Dry electrode film, dry negative electrode, and lithium battery including the same
Patent Information
- Application Number
- KR1020230053305
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-26
- Filing Date
- 2023-04-24
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-04-24
Smart Images

Figure 112023045802828-PAT00002_ABST
Abstract
Description
Technology Field
[0001] The invention relates to a dry cathode film, a dry cathode including the same, and a lithium battery. Background Technology
[0002] To meet the demands for miniaturization and high performance in various devices, high energy density is becoming important in addition to the miniaturization and weight reduction of lithium batteries. In other words, high-capacity lithium batteries are becoming crucial.
[0003] Electrodes manufactured from slurries containing solvents use an excess amount of solvent during electrode manufacturing, so dry methods that exclude the use of such organic solvents are being considered. The problem to be solved
[0004] One aspect is to provide a new dry cathode film having improved cycle characteristics by reducing internal resistance and enhancing mechanical strength.
[0005] Another aspect is to provide a dry cathode comprising the above-mentioned dry cathode film.
[0006] Another aspect is to provide a lithium battery comprising the above-mentioned dry cathode. means of solving the problem
[0007] Depending on one aspect,
[0008] A dry negative electrode active material and a dry binder are included, wherein the dry negative electrode active material comprises a core; and a shell disposed along the surface of the core, the core comprises a carbon-based material; a mixture of a carbon-based material and a silicon-based active material; a composite of a carbon-based material and a silicon-based active material; or a combination thereof, and the shell comprises a composite comprising one or more first metal oxides and a first carbon-based material, wherein the first metal oxide is disposed within a matrix of the first carbon-based material, and the first metal oxide is of the formula M a O b(0 <a≤3, 0<b<4, a가 1, 2, 또는 3 이면, b는 정수가 아님)로 표시되며, 상기 M은 원소주기율표 2족 내지 16족 중에서 선택된 하나 이상의 금속인, 건식 음극 필름이 제공된다.
[0009] According to another embodiment, a dry cathode is provided, comprising: a cathode current collector; and the above-described dry cathode film disposed on one or both sides of the cathode current collector.
[0010] The above-described cathode current collector comprises a substrate; and an interlayer disposed between the substrate and the dry cathode film, wherein the interlayer comprises a carbon-based conductive material.
[0011] According to another aspect, it includes an anode, a cathode, and an electrolyte placed between the anode and the cathode, and
[0012] The above-mentioned cathode is the dry cathode described above, and
[0013] A lithium battery is provided in which the above electrolyte comprises a liquid electrolyte, a solid electrolyte, or a combination thereof. Effects of the invention
[0014] According to one aspect, as the internal resistance of the dry cathode film is reduced and its mechanical properties are improved, the initial efficiency and cycle characteristics of a lithium battery employing such a dry cathode film are improved. Brief explanation of the drawing
[0015] FIG. 1 is a schematic cross-sectional view of a dry cathode active material according to one embodiment. FIG. 2 is a schematic cross-sectional view of a dry cathode active material according to another embodiment. FIG. 3a shows the structure of a dry cathode-separator subassembly according to one embodiment. FIG. 3b shows the structure of a dry cathode-separator subassembly according to another embodiment. FIG. 4a is a cross-sectional view showing the stacked structure of a dry negative electrode for a lithium battery according to one embodiment. FIG. 4b is a cross-sectional view showing a stacked structure of a dry negative electrode for a lithium battery according to another embodiment. FIG. 4c is a cross-sectional view showing a stacked structure of a dry negative electrode for a lithium battery according to another embodiment. Figure 5 is a schematic diagram of a lithium battery according to one embodiment. FIG. 6 is a schematic diagram of a lithium battery according to another embodiment. FIG. 7 is a schematic diagram of a lithium battery according to another embodiment. Specific details for implementing the invention
[0016] Various embodiments are illustrated in the accompanying drawings. However, the present creative concept may be embodied in many different forms and should not be interpreted as being limited to the embodiments described herein. Rather, these embodiments are provided to ensure that the present disclosure is thorough and complete and will sufficiently convey the scope of the present creative concept to those skilled in the art. Identical reference numerals denote identical components.
[0017] When it is stated that one component is "on top" of another component, it can be understood that it may be directly on top of the other component or that another component may be interposed between them. In contrast, when it is stated that a component is "directly on top" of another component, no component is interposed between them.
[0018] Terms such as "first," "second," "third," etc., may be used in this specification to describe various components, components, regions, layers, and / or zones, but these components, components, regions, layers, and / or zones should not be limited by these terms. These terms are used solely to distinguish one component, component, region, layer, or zone from another. Accordingly, the first component, component, region, layer, or zone described below may be referred to as the second component, component, region, layer, or zone without departing from the teachings of this specification.
[0019] The terms used herein are intended to describe specific embodiments only and are not intended to limit the creative idea. The singular form used herein is intended to include the plural form including "at least one" unless the content clearly indicates otherwise. "At least one" should not be interpreted as limiting to the singular. As used herein, the term "and / or" includes any combination of one or more of the listed items. The terms "comprising" and / or "comprising" as used in the detailed description specify the presence of the specified features, regions, integers, steps, actions, components, and / or components, and do not exclude the presence or addition of one or more other features, regions, integers, steps, actions, components, components, and / or groups thereof.
[0020] Spatially relative terms such as "bottom," "lower," "subordinate," "top," "upper," and "upper" may be used herein to facilitate the description of the relationship of one component or feature to another component or feature. Spatially relative terms are to be understood as intended to include different orientations of the device during use or operation in addition to the orientations depicted in the drawings. For example, if the device in the drawings is inverted, a component described as "bottom" or "lower" of another component or feature will be oriented to the "top" of that other component or feature. Thus, the exemplary term "bottom" may encompass both the upper and lower directions. The device may be positioned in different directions (it may be rotated 90 degrees or rotated in other directions), and spatially relative terms used herein may be interpreted accordingly.
[0021] Unless otherwise defined, all terms used in this specification (including technical and scientific terms) have the same meaning as generally understood by those skilled in the art to which this disclosure pertains. Furthermore, it will also be understood that terms as defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning within the context of the relevant technology and the content of this disclosure, and should not be interpreted in an idealized or overly formal sense.
[0022] Exemplary embodiments are described herein with reference to cross-sectional views, which are schematic diagrams of idealized embodiments. As such, variations from the depicted shapes should be expected as a result of, for example, manufacturing techniques and / or tolerances. Accordingly, the embodiments described herein should not be interpreted as being limited to the specific shapes of the regions as depicted herein, but should include variations in shapes resulting from, for example, manufacturing. For example, a region depicted or described as flat may typically have rough and / or non-linear features. Furthermore, an angle depicted as sharp may be rounded. Accordingly, the regions depicted in the drawings are essentially schematic, and the shapes are not intended to depict the exact shape of the region and are not intended to limit the scope of the claims.
[0023] "Group" refers to a group of elements in the periodic table according to the International Union of Pure and Applied Chemistry ("IUPAC") group classification system of groups 1-18.
[0024] In this specification, "particle diameter" refers to the average diameter when the particles are spherical and the average major axis length when the particles are non-spherical. The particle diameter can be measured using a particle size analyzer (PSA). "Particle diameter" is, for example, the average particle diameter. The "average particle diameter" is, for example, D50, the median particle diameter.
[0025] D50 is the particle size corresponding to 50% of the cumulative volume calculated from the side of the particle with the smaller particle size in the particle size distribution measured by laser diffraction.
[0026] D90 is the particle size corresponding to the 90% cumulative volume calculated from the side of the particle with the smaller particle size in the particle size distribution measured by laser diffraction.
[0027] D10 is the particle size corresponding to the 10% cumulative volume calculated from the side of the particle with the smaller particle size in the particle size distribution measured by laser diffraction.
[0028] In the present disclosure, “metal” includes both metals and metalloids such as silicon and germanium in an elemental or ionic state.
[0029] In this disclosure, "alloy" means a mixture of two or more metals.
[0030] In the present disclosure, "electrode active material" refers to an electrode material capable of undergoing lithiation and delithiation.
[0031] In the present disclosure, "anode active material" refers to an anode material capable of undergoing lithiation and delithiation.
[0032] In the present disclosure, "anode active material" refers to an anode material capable of undergoing lithiation and delithiation.
[0033] In the present disclosure, "lithiation" and "to lithiate" refer to the process of adding lithium to an electrode active material.
[0034] In the present disclosure, "delithiation" and "to delithiate" refer to the process of removing lithium from an electrode active material.
[0035] In this disclosure, "charge" and "to charge" refer to the process of providing electrochemical energy to a battery.
[0036] In this disclosure, "discharge" and "discharge" refer to the process of removing electrochemical energy from a battery.
[0037] In this disclosure, "anode" and "cathode" refer to electrodes where electrochemical reduction and lithiation occur during the discharge process.
[0038] In this disclosure, "cathode" and "anode" refer to electrodes where electrochemical oxidation and delithiation occur during the discharge process.
[0039] Although specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are not currently anticipated or cannot be anticipated may arise to the applicant or those skilled in the art. Accordingly, the appended claims, which may be filed and modified, are intended to include all such alternatives, modifications, variations, improvements, and substantial equivalents.
[0041] A dry cathode film according to exemplary embodiments, a dry cathode including the same, and a lithium battery are described in more detail below.
[0042] When an active material, a conductive material, and a binder are mixed dry to fabricate a cathode plate using a dry cathode, the conductive material in the form of nanoparticles is bound to the binder, and an excessive amount of the conductive material aggregates in the binder and binds to the active material. This results in non-uniform mixing of the active material, conductive material, and binder, leading to high electrode plate resistance and low tensile strength. To solve this problem, a dry cathode film is provided in which the binder and the conductive material are uniformly bound to the surface of the active material during the dry electrode plate manufacturing process. This provides a dry cathode film with improved resistance reduction and enhanced tensile strength, as well as a dry cathode and a lithium battery containing the same.
[0043] A dry cathode film according to one embodiment comprises a dry cathode active material and a dry binder, wherein the dry cathode active material comprises a core; and a shell disposed along the surface of the core, wherein the core comprises a carbon-based material; a mixture of a carbon-based material and a silicon-based active material; a composite of a carbon-based material and a silicon-based active material; or a combination thereof, and wherein the shell contains a composite comprising one or more first metal oxides and a first carbon-based material, wherein the first metal oxide is disposed within a matrix of the first carbon-based material, and the first metal oxide has the chemical formula M a O b(0 <a≤3, 0<b<4, a가 1, 2, 또는 3 이면, b는 정수가 아님)로 표시되며, 상기 M은 원소주기율표 2족 내지 16족 중에서 선택된 하나 이상의 금속이다.
[0044] Referring to FIG. 1, the dry cathode active material (100) includes a core (10) and a shell (20) arranged continuously or discontinuously along the surface of the core (10).
[0045] The core (10) contains a carbon-based material; a mixture of a carbon-based material and a silicon-based active material; a composite of a carbon-based material and a silicon-based active material; or a combination thereof, and the shell (20) may cover all or part of the core (10).
[0046] The shell (20) comprises a first metal oxide (21) and a first carbon-based material (22). The dry cathode active material is, for example, an electrode active material that is not impregnated, dissolved, or dispersed in a process solvent during the manufacturing process of a dry cathode film.
[0047] The dry cathode active material has a core / shell structure, and since the shell includes a first carbon-based material, the dry cathode active material and the dry binder can be mixed more uniformly. Accordingly, aggregation of the dry binder within the dry cathode film is suppressed, and the dry binder can be uniformly distributed in three dimensions. As local resistance regions within the dry cathode film are suppressed, the imbalance of current density is reduced, and the overall internal resistance of the electrolytic electrode film can be reduced.
[0048] The interface resistance between the dry negative electrode active material and the dry negative electrode active material can be reduced by the dry negative electrode active material having a core / shell structure and the shell including a first carbon-based material. The internal resistance of the dry negative electrode film can be reduced by the dry negative electrode active material having a core / shell structure and the shell including a first carbon-based material. The binding strength between the dry negative electrode active material and the dry binder can be improved by the dry negative electrode active material having a core / shell structure and the shell including a first carbon-based material. Mechanical properties such as the tensile strength of the dry negative electrode film can be improved by the dry composite negative electrode active material having a core / shell structure and the shell including a first carbon-based material. As the internal resistance of the dry negative electrode film is reduced and mechanical properties are improved, the cycle characteristics of a lithium battery containing such a dry negative electrode film can be improved.
[0049] The ion conductivity of the shell can be improved compared to a shell made of carbon-based material by including a first metal oxide, and consequently, the ion conductivity of the dry cathode active material can be improved.
[0050] The dry cathode active material has a core / shell structure, and the shell may be disposed continuously or discontinuously along the surface of the core. The shell may be disposed more uniformly on the core by including a first metal oxide disposed in a first carbon-based material matrix. The shell may be disposed more uniformly on the core without aggregation by, for example, being introduced onto the core from a composite containing a first metal oxide disposed in a first carbon-based material matrix. By effectively blocking contact between the core and the electrolyte with the shell uniformly disposed on the core, side reactions caused by contact between the core and the electrolyte can be prevented. Furthermore, the formation of a resistive layer on the core surface can be suppressed by suppressing cation mixing caused by contact between the core and the electrolyte. Additionally, by introducing the shell onto the core, the leaching of transition metal ions from the core can be suppressed in a core containing a transition metal. The first carbon-based material may be, for example, a crystalline carbon-based material. The first carbon-based material may be, for example, a carbon-based nanostructure. The first carbon-based material may be, for example, a carbon-based two-dimensional nanostructure. The first carbon-based material may be, for example, graphene. For example, a shell containing graphene and / or a matrix thereof possesses flexibility, thereby easily accommodating volume changes of the dry anode active material during charging and discharging, which suppresses the occurrence of cracks within the dry anode active material. Since graphene has high electronic conductivity, the interfacial resistance between the dry anode active material and the electrolyte is reduced. Therefore, the increase in the internal resistance of the lithium battery can be suppressed despite the introduction of a shell containing graphene. In contrast, conventional carbon-based materials that do not contain the first metal oxide are difficult to distribute uniformly on the core of the dry anode active material because they easily aggregate.In addition, since the first carbon-based material matrix is derived from, for example, a graphene matrix, it has a relatively lower density and higher porosity compared to conventional carbon-based materials derived from graphite-based materials.
[0051] The dry cathode active material has a core / shell structure. The shell comprises a first metal oxide, and the metal included in the first metal oxide may be one or more selected from, for example, Al, Nb, Mg, Sc, Ti, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn, Sb, and Se. The first metal oxide is, for example, Al2O z (0 <z<3), NbO x (0 <x<2.5), MgO x (0 <x<1), Sc2O z (0 <z<3), TiO y (0 <y<2), ZrO y (0 <y<2), V2O z (0 <z<3), WO y (0 <y<2), MnO y (0 <y<2), Fe2O z (0 <z<3), Co3O w (0 <w<4), PdO x (0 <x<1), CuO x (0 <x<1), AgO x (0 <x<1), ZnO x (0 <x<1), Sb2O z (0 <z<3), 및 SeO y (0 <y<2) 중에서 선택된 하나 이상일 수 있다. 제1 탄소계 재료 메트릭스 내에 이러한 제1 금속산화물이 배치됨에 의하여 코어 상에 배치된 쉘의 균일성이 향상되고, 건식 음극활물질의 내전압성(high-voltage resistance)이 더욱 향상된다. 쉘은 예를 들어 제1 금속산화물로서 Al2O x (0 <x<3)를 포함한다.
[0052] The shell may further include one or more second metal oxides. The second metal oxide is, for example, of the formula Ma O c (0 <a≤3, 0<c≤4, a가 1, 2, 또는 3이면, c는 정수임)로 표시될 수 있으며, 상기 M은 원소주기율표 2족 내지 13족, 제15족 및 16족 중에서 선택된 하나 이상의 금속이다. 제2 금속산화물은 예를 들어 상기 제1 금속산화물과 동일한 금속을 포함할 수 있다. 제2 금속산화물의 a 와 c의 비율인 c / a가 상기 제1 금속산화물의 a 와 b의 비율인 b / a에 비하여 더 큰 값을 가질 수 있다. 예를 들어, c / a > b / a. The second metal oxide may be disposed within the first carbon-based material matrix. The second metal oxide is selected from, for example, Al2O3, NbO, NbO2, Nb2O5, MgO, Sc2O3, TiO2, ZrO2, V2O3, WO2, MnO2, Fe2O3, Co3O4, PdO, CuO, AgO, ZnO, Sb2O3, and SeO2. The first metal oxide is, for example, a reduction product of the second metal oxide. The first metal oxide is obtained by reducing part or all of the second metal oxide. Thus, the first metal oxide has a lower oxygen content and a lower oxidation number of the metal compared to the second metal oxide. For example, the shell is Al2O, which is the first metal oxide. x (0 <x<3) 및 제2 금속산화물인 Al2O3를 포함한다.
[0053] The shell comprises, for example, one or more selected from a first metal oxide and a second metal oxide, and the particle size of one or more selected from the first metal oxide and the second metal oxide may be, for example, 0.1 nm to 100 nm, 0.5 nm to 100 nm, 1 nm to 100 nm, 1 nm to 50 nm, 1 nm to 30 nm, 5 nm to 30 nm, or 10 nm to 30 nm. By having particle sizes in this nano range, the first metal oxide and / or the second metal oxide can be distributed more uniformly within the first carbon-based material matrix. If the particle size of one or more of the first metal oxide and the second metal oxide increases excessively, the internal resistance of the composite cathode active material may increase as the thickness of the shell increases. If the particle size of one or more of the first metal oxide and the second metal oxide decreases excessively, uniform dispersion may be difficult.
[0054] The shell comprises a first metal oxide and / or a second metal oxide and may comprise a first carbon-based material. The first carbon-based material may be positioned in a direction protruding from the surface of the first metal oxide and / or the second metal oxide. The first carbon-based material may be positioned in a direction protruding from the surface of the first metal oxide and / or the second metal oxide by growing straight from the surface of the first metal oxide and / or the second metal oxide. The first carbon-based material positioned in a direction protruding from the surface of the first metal oxide and / or the second metal oxide is, for example, a carbon-based two-dimensional nanostructure, a carbon-based flake, or graphene.
[0055] The thickness of the shell is 5 μm or less, for example, 0.1 nm to 5 μm, 0.5 nm to 5 μm, 1 nm to 5 μm, 1 nm to 1 μm, 1 nm to 500 nm, 1 nm to 200 nm, 1 nm to 100 nm, 1 nm to 50 nm, 1 nm to 30 nm, or 1 nm to 20 nm. By having the shell within this range of thickness, the electronic conductivity of the dry cathode containing the dry cathode active material can be further improved and the internal resistance can be further reduced.
[0056] The shell may have a single-layer structure or a multi-layer structure. The multi-layer structure may have, for example, a two-layer structure, a three-layer structure, or a four-layer structure. In the multi-layer structure, for example, the type of metal of the first metal oxide contained in each layer may be different.
[0057] The content of the shell may be, for example, 5 wt% or less, 0.01 wt% to 5 wt%, 0.01 wt% to 3 wt%, 0.01 wt% to 2 wt%, or 0.01 wt% to 1 wt% of the total weight of the dry negative electrode active material. The content of the first metal oxide may be, for example, 3 wt% or less, 0.006 wt% to 3 wt%, 0.06 wt% to 1.8 wt%, 0.006 wt% to 1.2 wt%, or 0.006 wt% to 0.6 wt% of the total weight of the dry negative electrode active material. By including the shell and the first metal oxide within these content ranges, the cycle characteristics of the lithium battery are further improved.
[0058] A shell disposed along the surface of the core is, for example, a dry coating layer. The shell may be introduced onto the core by a dry method, for example, milling. The shell disposed along the surface of the core may comprise one or more selected from, for example, a composite comprising a first metal oxide and a first carbon-based material, for example, graphene, and the milling result of said composite. The first metal oxide is disposed within a matrix of the first carbon-based material, for example, a graphene matrix.
[0059] The shell is manufactured from a composite comprising, for example, a first metal oxide and a first carbon-based material, for example, graphene. The composite may further comprise a second metal oxide in addition to the first metal oxide. The composite may comprise, for example, two or more first metal oxides. The composite may comprise, for example, two or more first metal oxides and two or more second metal oxides.
[0060] The composite may include one or more selected from a first metal oxide and a second metal oxide. The particle size of one or more selected from the first metal oxide and the second metal oxide may be 0.1 nm to 100 nm, 0.5 nm to 100 nm, 1 nm to 100 nm, 1 nm to 50 nm, 1 nm to 30 nm, 5 nm to 30 nm, or 10 nm to 30 nm. By having particle sizes in this nano range, the first metal oxide and / or the second metal oxide can be distributed more uniformly within the first carbon-based material matrix of the composite. Thus, the composite can be uniformly coated on the core without aggregation to form a shell. Additionally, by having particle sizes in this range, the first metal oxide and / or the second metal oxide can be more uniformly disposed on the core. Therefore, by uniformly distributing the first metal oxide and / or the second metal oxide on the core, the withstand voltage characteristics can be exhibited more effectively. The particle size of the first metal oxide and / or the second metal oxide is measured using a measuring device, for example, a laser diffraction method or a dynamic light scattering method. The particle size is measured using, for example, a laser scattering particle size distributor (e.g., Horibasa LA-920) and is the value of the median particle size (D50) when 50% is accumulated from the small particle side in volume conversion. One or more selected from the first metal oxide and / or the second metal oxide may have a uniformity deviation of 3% or less, 2% or less, or 1% or less.
[0061] Uniformity can be obtained, for example, by XPS. Thus, one or more selected from the first metal oxide and the second metal oxide can be uniformly distributed within the composite with a deviation of 3% or less, 2% or less, or 1% or less.
[0062] A dry cathode active material comprises a core, wherein the core comprises, for example, a carbon-based material; a mixture of a carbon-based material and a silicon-based active material; a composite of a carbon-based material and a silicon-based active material; or a combination thereof.
[0063] The content of the silicon-based active material in the mixture of the carbon-based material and the silicon-based active material or the composite of the carbon-based material and the silicon-based active material is 5 to 20 weight%, 7 to 18 weight%, 10 to 17 weight%, or 10 to 15 weight% based on 10 weight% of the total weight of the mixture of the carbon-based material and the silicon-based active material or the composite of the carbon-based material and the silicon-based active material.
[0064] The carbon-based material is crystalline carbon, amorphous carbon, or a combination thereof, wherein the crystalline carbon is one or more selected from the group consisting of natural graphite, synthetic graphite, graphene, fullerene, and carbon nanotubes, and the amorphous carbon is one or more selected from the group consisting of pitch carbon, soft carbon, hard carbon, mesophase pitch carbide, calcined coke, and carbon fibers.
[0065] The precursor of the above amorphous carbon may be coal-based pitch, mesophase pitch, petroleum-based pitch, coal-based oil, petroleum-based heavy oil, or polymer resins such as phenolic resin, furan resin, or polyimide resin.
[0066] The above silicon-based active material is a Si alloy, a silicon-containing structure, a silicon-containing compound, or a combination thereof.
[0067] The above silicon-containing compound is SiOx (0 <x<2), SiC, 또는 그 조합이며, 상기 실리콘 함유 구조체가 실리콘 복합 구조체를 포함한다.
[0068] According to one embodiment, the silicon composite structure may be a silicon-carbon composite.
[0069] The silicon-carbon composite is a silicon-carbon composite comprising silicon particles and a first carbon-based material, a silicon-carbon composite comprising a core mixed with silicon particles and a second carbon-based material and a third carbon-based material surrounding the core, or a combination thereof.
[0070] The first to third carbon-based materials are independently crystalline carbon, amorphous carbon, or a combination thereof. The silicon-carbon composite comprises a core containing silicon particles and crystalline carbon, and an amorphous carbon coating layer located on the surface of the core.
[0071] When the silicon-carbon composite described above is used as a silicon-based active material, the secondary battery can exhibit high capacity and achieve stable cycle characteristics.
[0072] In the silicon-carbon composite comprising the silicon particles and the first carbon-based material, the content of the silicon particles may be 30 wt% to 70 wt%, 30 wt% to 60 wt%, for example, 40 wt% to 50 wt%. Alternatively, the silicon-based active material may comprise a silicon-carbon composite comprising a core mixed with silicon particles and a second carbon-based material and a third carbon-based material surrounding the core. Using such a silicon-carbon composite allows a secondary battery to achieve a very high capacity while improving capacity retention and, in particular, enhancing high-temperature life characteristics. In this specification, the average particle size (D50) refers to the diameter of a particle whose cumulative volume in the particle size distribution is 50 wt%.
[0073] In addition, with respect to 100 weight% of the silicon-carbon composite, the third carbon-based material may be included in an amount of 1 weight% to 50 weight%, and silicon particles may be included in an amount of 30 weight% to 70 weight%. The second carbon-based material may be included in an amount of 20 weight% to 69 weight%. When the content of silicon particles, the third carbon-based material, and the second carbon-based material falls within the above ranges, the discharge capacity of the secondary battery is excellent and the capacity retention rate is improved.
[0074] The particle size of the silicon particles is 10 nm to 30 µm, for example, 10 nm to 1000 nm, or 20 nm to 150 nm. When the average particle size of the silicon particles falls within the above range, volume expansion occurring during charging and discharging can be suppressed, and interruption of electron movement due to particle fragmentation during charging and discharging can be prevented.
[0075] In the above silicon-carbon composite, for example, the second carbon-based material may be crystalline carbon and the third carbon-based material may be amorphous carbon. That is, the above silicon-carbon composite is a silicon-carbon composite comprising a core containing silicon particles and crystalline carbon and an amorphous carbon coating layer located on the surface of the core.
[0076] A silicon-carbon composite can be, for example, a silicon-carbon nanocomposite. A silicon-carbon nanocomposite refers to a composite in which one or more of silicon and carbon have a nanoscale size of less than 1 μm. For example, a silicon-carbon nanocomposite can be a composite in which silicon nanoparticles and carbon nanoparticles are combined.
[0077] Silicon-containing compounds may include, for example, silicon, silicon alloys, silicon oxides, silicon nitrides, silicon nitrates, silicon carbides, or combinations thereof. Silicon-containing compounds are, for example, SiO₂ x (0 <x<2)를 포함할 수 있다.
[0078] The silicon alloy comprises silicon and elements such as alkali metals, alkaline earth metals, elements of groups 13 to 16, transition metals, rare earth elements, or combinations thereof. The elements are, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, or combinations thereof.
[0079] According to another embodiment, the silicon composite structure comprises: porous silicon secondary particles; and a first carbon flake disposed on the porous silicon secondary particles; wherein the porous silicon secondary particles are aggregates of a plurality of silicon composite primary particles, and the silicon composite primary particles comprise silicon; and silicon suboxide (SiO₂) disposed on the silicon. x , 0 <x<2); 및 상기 실리콘 서브옥사이드 상에 배치되는 제2 탄소 플레이크를 포함할 수 있다.
[0080] A silicon composite structure comprises a porous silicon secondary particle containing an agglomerate of a plurality of silicon composite primary particles and a first carbon flake disposed on said porous silicon secondary particle. The first carbon flake disposed on the porous silicon secondary particle may be disposed to cover at least one surface of the porous silicon secondary particle. The first carbon flake may be disposed directly on the porous silicon secondary particle. The first carbon flake may be grown directly on the silicon suboxide of the porous silicon secondary particle. The first carbon flake may be grown directly from the surface of the porous silicon secondary particle and disposed directly on the surface of the porous silicon secondary particle. The first carbon flake may cover the surface of the porous silicon secondary particle wholly or partially. The coverage rate of the first carbon flake is, for example, 5 to 100%, 10 to 99%, 20 to 95%, or 40 to 90% based on the total surface area of the porous silicon secondary particle. The carbon of the first carbon flake is present on the surface of the porous silicon secondary particle and effectively buffers the volume change of the porous silicon secondary particle. The size of the porous silicon secondary particle may be, for example, 1 to 20 µm, 2 to 18 µm, or 3 to 10 µm. The size of the first carbon flake may be, for example, 1 to 200 nm, 5 to 150 nm, or 10 to 100 nm. Here, size refers to the diameter or major axis length.
[0081] The silicon composite primary particles are silicon; silicon silicon suboxide (SiO₂) disposed on at least one surface of the silicon. x, 0<x<2); 및 상기 실리콘 서브옥사이드의 일면 상에 배치된 제2 탄소 플레이크를 포함한다. 실리콘은 예를 들어, 판상형, 침상형, 구형, 또는 이들의 조합 형태일 수 있다. 실리콘은 그 형상이 특별하게 제한되지 않으며, 예를 들어 스피어, 나노와이어, 침상, 막대형, 입자, 나노튜브, 나노로드, 웨이퍼(wafer), 및 나노리본, 또는 이들의 조합물이다. 실리콘의 평균 사이즈는 예를 들어 10 nm 내지 1 ㎛, 10 nm 내지 500 nm, 20 내지 150 nm, 또는 100 nm 이다. 실리콘의 평균 사이즈는 실리콘이 구형 입자인 경우에는 평균입경이고, 비구형 입자, 예를 들어 판상 입자 또는 침상형 입자인 경우에는 장축 길이, 길이 또는 두께를 의미할 수 있다. 실리콘 복합체 일차 입자에서 실리콘 상에 배치되는 실리콘 서브옥사이드(SiOx) (0<x<2)는 실리콘의 적어도 일면을 커버하도록 배치될 수 있다. 실리콘 서브옥사이드는 실리콘 상에 직접적으로 배치될 수 있다. 실리콘 서브옥사이드는 실리콘의 표면을 전체적으로 또는 부분적으로 커버할 수 있다. 실리콘 서브옥사이드의 커버율은 예를 들어 실리콘의 전체 표면적을 기준으로 하여 예를 들어 1 내지 100 %, 5 내지 99 %, 10 내지 95 %, 또는 20 내지 90 % 일 수 있다. 실리콘 서브옥사이드 상에 배치되는 제2 탄소 플레이크는 실리콘 서브옥사이드의 적어도 일 면을 커버하도록 배치될 수 있다. 제2 탄소 플레이크는 실리콘 서브옥사이드 상에 직접적으로 배치될 수 있다. 제2 탄소 플레이크는 상기 실리콘 서브옥사이드의 표면으로부터 직성장되어 실리콘 서브옥사이드의 표면에 직접적으로 배치될 수 있다. 제2 탄소 플레이크는 예를 들어 실리콘 서브옥사이드의 표면을 전체적으로 또는 부분적으로 커버할 수 있다.The coverage rate of the second carbon flake may be, for example, 10 to 100%, 10 to 99%, 20 to 95%, or 40 to 90% based on the total surface area of the silicon suboxide. The carbon of the second carbon flake is present on the surface of the silicon and / or silicon suboxide and can effectively buffer volume changes of the silicon composite primary particles. The size of the second carbon flake may be, for example, 1 to 200 nm, 5 to 150 nm, or 10 to 100 nm. Here, size refers to the diameter or major axis length.
[0082] The silicon composite structure comprises porous silicon secondary particles and a second carbon flake disposed on the porous silicon secondary particles. The second carbon flake may be disposed in a manner that wholly or partially covers the porous silicon secondary particles. For example, the second carbon flake may be disposed in a manner that wholly or partially surrounds the porous silicon secondary particles. The porous silicon secondary particles comprise a first carbon flake disposed on the silicon composite primary particles. During volume expansion / contraction of the silicon composite structure, the silicon contained in the porous silicon secondary particles may maintain contact with the first carbon flake and / or the second carbon flake. Since the porous secondary particles contain pores, they may act as an internal buffer space during volume expansion / contraction of the silicon composite structure. Therefore, unlike conventional silicon-based negative electrode active materials, the silicon composite structure can effectively accommodate volume changes of the silicon composite structure during charging and discharging while suppressing an increase in internal resistance.
[0083] The porosity of the silicon composite structure may be, for example, 60% or less, or 30% to 60%. Alternatively, the silicon composite structure may be non-porous. The non-porous structure may have a porosity of, for example, 10% or less, or 5% or less. The non-porous structure may have a porosity of, for example, 0.01% to 5%, or 0%. The porosity may be measured by mercury adsorption (porosimetry) or nitrogen adsorption.
[0084] The silicon composite structure may have a non-spherical shape, for example. The sphericity of the silicon composite structure may be, for example, 0.9 or less. The sphericity of the silicon composite structure is, for example, 0.7 to 0.9, 0.8 to 0.9, or 0.85 to 0.9. The sphericity is, for example, 4πA / P 2 It is determined by (A is the area, P is the perimeter).
[0085] The silicon composite structure comprises a first carbon flake and a second carbon flake. The first carbon flake and the second carbon flake may be, for example, identical carbon flakes. The first carbon flake and the second carbon flake may be any carbon-based material having a flake shape. The first carbon flake and the second carbon flake may independently be graphene, graphite, carbon fiber, graphitic carbon, graphene oxide, or a mixture thereof. The porous composite structure may comprise, for example, a first graphene and a second graphene as the first carbon flake and the second carbon flake. The first graphene and the second graphene may each have a structure such as a nanosheet, a membrane (or film), or a flake. A nanosheet refers to a form formed in an irregular state on silicon suboxide or porous silicon secondary particles with a thickness of about 1000 nm or less, for example, 1 to 1000 nm. A film refers to a form continuously and uniformly formed on silicon suboxide or porous silicon secondary particles.
[0086] The silicon-containing structure may further include a carbon-based coating layer disposed on the silicon composite structure. The carbon-based coating layer can improve the physical stability of the silicon composite structure and more effectively prevent adverse reactions between silicon and the electrolyte during charging and discharging. The carbon-based coating layer may include, for example, a first amorphous carbon. The carbon-based coating layer may include a high-density first amorphous carbon. The first amorphous carbon may include, for example, pitch carbon, soft carbon, hard carbon, mesophase pitch carbide, calcined coke, carbon fiber, or a mixture thereof. The carbon-based coating layer may further include crystalline carbon. By including crystalline carbon in the carbon-based coating layer, it can more effectively perform a buffering role against volume changes of the silicon composite structure. The crystalline carbon may be, for example, natural graphite, synthetic graphite, graphene, fullerene, carbon nanotubes, or a mixture thereof. The thickness of the carbon-based coating layer can be, for example, 1 nm to 5000 nm, 10 nm to 2000 nm, or 5 nm to 2500 nm.
[0087] The silicon-containing structure may further include, for example, a second amorphous carbon disposed within a silicon composite structure. For example, the silicon composite structure may include porous silicon secondary particles, and the second amorphous carbon may be disposed within the pores of the porous silicon secondary particles. The second amorphous carbon may be disposed between a plurality of silicon composite primary particles constituting the porous silicon secondary particles. The silicon composite primary particles are, for example, silicon; silicon suboxide (SiO₂) disposed on the silicon. x, 0 <x<2); 및 실리콘 서브옥사이드 상에 배치되는 제2 탄소 플레이크; 및 제2 탄소 플레이크 상에 배치되는 제2 비정질 탄소를 포함할 수 있다. 실리콘 복합 구조체는 그 내부의 기공에 치밀한 제2 비정질 탄소가 채워짐에 의하여 비다공성 구조를 갖는 밀집 구조체를 가질 수 있다. 실리콘 복합 구조체가 이러한 비다공성 구조를 가짐에 의하여, 충방전시 전해액과의 부반응이 더욱 감소될 수 있으며, 실리콘의 부피 변화를 더욱 효과적으로 완화할 수 있다. 제2 비정질 탄소는 예를 들어 피치카본, 소프트카본, 하드카본, 메조페이스 피치 탄화물, 소성된 코크스, 탄소섬유 또는 이들의 혼합물을 포함할 수 있다.
[0088] In a silicon composite structure, the mixing ratio of the total weight of the first carbon, which is the sum of the carbon of the first carbon flake and the carbon of the second carbon flake, and the weight of the second carbon, which is the carbon of the carbon-based coating layer, may be, for example, 30:1 to 1:3, 20:1 to 1:1, or 10:1 to 1:0.9. By having the first carbon and the second carbon in this range of mixing ratios, a lithium battery having improved cycle characteristics can be provided. The mixing ratio of the first carbon and the second carbon can be confirmed through thermogravimetric analysis. The first carbon is associated with a peak appearing in the region of 700 to 750 °C, and the second carbon is associated with a peak appearing in the region of 600 to 650 °C. Thermogravimetric analysis is performed, for example, in an air atmosphere at a heating rate of about 10 °C / min in the range of 25 to 1,000 °C. The first carbon is, for example, crystalline carbon, and the second carbon is, for example, amorphous carbon. The mixing ratio of the total weight of the carbon of the first carbon flake and the carbon of the second carbon flake, and the total weight of the first amorphous carbon and the second amorphous carbon, may be, for example, 1:99 to 99:1, 1:20 to 80:1, or 1:1 to 1:10.
[0089] The core is a silicon-containing negative electrode active material, which is a silicon-containing compound, SiO₂. x (0 <x<2)를 포함할 수 있다. SiO x (0 <x<2)의 평균 입경은 예를 들어 1 ㎛ 이상, 3 ㎛ 이상, 또는 5 ㎛ 이상일 수 있다. SiO x (0 <x<2)의 평균 입경은 예를 들어 1 ㎛ 내지 30 ㎛, 3 ㎛ 내지 20 ㎛, 또는 5 ㎛ 내지 15 ㎛ 일 수 있다.
[0090] The shell contains a composite comprising a first metal oxide; and a first carbon-based material.
[0091] Since the first carbon-based material, for example graphene, has high electronic conductivity, it can reduce the interfacial resistance between the dry negative electrode active material and the electrolyte. Therefore, the increase in the internal resistance of the lithium battery is suppressed despite the introduction of a shell containing the first carbon-based material.
[0092] Since the first carbon-based material included in the shell is derived from a graphene matrix, it has a relatively lower density and a higher porosity compared to conventional carbon-based materials derived from graphite-based materials. The d002 interplanar distance of the first carbon-based material included in the shell of the dry cathode active material may be, for example, 3.38 Å or more, 3.45 Å or more, 3.50 Å or more, 3.60 Å or more, 3.80 Å or more, or 4.00 Å or more. The d002 interplanar distance of the first carbon-based material included in the shell of the dry cathode active material may be, for example, 3.38 to 4.0 Å, 3.38 to 3.8 Å, 3.38 to 3.6 Å, 3.38 to 3.5 Å, or 3.38 to 3.45 Å. In contrast, the d002 interplanar distance of a conventional carbon-based material derived from a graphite-based material may be, for example, 3.38 Å or less, or 3.35 to 3.38 Å. Since the first metal oxide has dielectric strength, it can prevent the deterioration of the core during charging and discharging at high voltage. The shell may include, for example, one type of first metal oxide or two or more different types of first metal oxides. As a result, the cycle characteristics of a lithium battery containing the above-described dry negative electrode active material are improved, and volume change can be suppressed.
[0093] The shell may comprise, for example, a first carbon-based material, and the core may comprise, for example, a silicon-containing structure and / or a silicon-containing compound as a silicon-containing negative electrode active material. For example, the first carbon-based material may be composited with the silicon-containing structure and / or silicon-containing compound through a mechanochemical reaction. The first carbon-based material may be chemically bonded with, for example, the silicon-containing structure and / or silicon-containing compound through chemical bonding. The core and the shell are composited by the first carbon-based material disposed in the shell and the silicon-containing structure and / or silicon-containing compound disposed in the core being chemically bonded through chemical bonding. Thus, the composite negative electrode active material is distinguished from a simple physical mixture of the first carbon-based material and the silicon-containing structure and / or silicon-containing compound. The first metal oxide and the carbon-based material contained in the shell may also be chemically bound through chemical bonding. Here, the chemical bonding is, for example, a covalent bond or an ionic bond.
[0094] The composite comprises a first carbon-based material. The first carbon-based material has, for example, a branched structure, and one or more metal oxides selected from a first metal oxide and a second metal oxide may be distributed within the branched structure of the first carbon-based material. The branched structure of the first carbon-based material comprises, for example, a plurality of first carbon-based material particles in contact with one another. By having a branched structure of the first carbon-based material, various conductive paths can be provided. The first carbon-based material may be, for example, graphene. Graphene has, for example, a branched structure, and one or more metal oxides selected from a first metal oxide and a second metal oxide may be distributed within the branched structure of the graphene. The branched structure of the graphene comprises, for example, a plurality of graphene particles in contact with one another. By having a branched structure of the graphene, various conductive paths can be provided.
[0095] The first carbon-based material has, for example, a spherical structure, and one or more metal oxides selected from the first metal oxide and the second metal oxide may be distributed within the spherical structure. The size of the spherical structure of the first carbon-based material may be 50 nm to 300 nm. There may be multiple first carbon-based materials having a spherical structure. As the first carbon-based material has a spherical structure, the composite may have a rigid structure. The first carbon-based material may be, for example, graphene. Graphene has, for example, a spherical structure, and one or more metal oxides selected from the first metal oxide and the second metal oxide may be distributed within the spherical structure. The size of the spherical structure of the graphene may be 50 nm to 300 nm. There may be multiple graphenes having a spherical structure. As the graphene has a spherical structure, the composite may have a rigid structure.
[0096] The first carbon-based material has, for example, a spiral structure in which a plurality of spherical structures are connected, and one or more metal oxides selected from the first metal oxide and the second metal oxide may be distributed within the spherical structure of the spiral structure. The size of the spiral structure of the first carbon-based material may be 500 nm to 100 μm. As the first carbon-based material has a spiral structure, the composite may have a rigid structure. The first carbon-based material may be, for example, graphene. The graphene has, for example, a spiral structure in which a plurality of spherical structures are connected, and one or more metal oxides selected from the first metal oxide and the second metal oxide may be distributed within the spherical structure of the spiral structure. The size of the spiral structure of the graphene may be 500 nm to 100 μm. As the graphene has a spiral structure, the composite may have a rigid structure.
[0097] The first carbon-based material has, for example, a cluster structure in which a plurality of spherical structures are aggregated, and one or more metal oxides selected from the first metal oxide and the second metal oxide may be distributed within the spherical structure of the cluster structure. The size of the cluster structure of the first carbon-based material may be 0.5 mm to 10 cm. As the first carbon-based material has a cluster structure, the composite may have a rigid structure. The first carbon-based material may be, for example, graphene. Graphene has, for example, a cluster structure in which a plurality of spherical structures are aggregated, and one or more metal oxides selected from the first metal oxide and the second metal oxide may be distributed within the spherical structure of the cluster structure. The size of the cluster structure of graphene may be 0.5 mm to 10 cm. As graphene has a cluster structure, the composite may have a rigid structure.
[0098] The composite is, for example, a faceted-ball structure, and one or more selected from the first metal oxide and the second metal oxide may be distributed inside or on the surface of the structure. Since the composite is such a faceted-ball structure, the composite can be easily coated on the irregular surface of the core.
[0099] The composite is, for example, a planar structure, and one or more selected from the first metal oxide and the second metal oxide may be distributed inside or on the surface of the planar structure. Since the composite is such a two-dimensional planar structure, the composite can be easily coated on the irregular surface of the core.
[0100] The first carbon-based material extends from the first metal oxide by a distance of 10 nm or less and may include at least 1 to 20 layers of the first carbon-based material. For example, a first carbon-based material having a total thickness of 12 nm or less may be disposed on the first metal oxide by stacking a plurality of layers of the first carbon-based material. For example, the total thickness of the carbon-based material may be 0.6 nm to 12 nm. The first carbon-based material may be, for example, graphene. The graphene extends from the first metal oxide by a distance of 10 nm or less and may include at least 1 to 20 layers of graphene. For example, graphene having a total thickness of 12 nm or less may be disposed on the first metal oxide by stacking a plurality of layers of graphene. For example, the total thickness of the graphene may be 0.6 nm to 12 nm.
[0101] The shell may further include a second carbon-based material which is fibrous carbon. The second carbon-based material may include fibrous carbon.
[0102] By further including a second carbon-based material in which the shell is fibrous carbon, the conducting path of the composite cathode active material can be further extended. The second carbon-based material can form a three-dimensional conductive network between multiple composite cathode active materials, thereby reducing the internal resistance of the cathode containing the composite cathode active material. By fixing fibrous carbon on the composite cathode active material, a uniform and stable three-dimensional conductive network can be formed between multiple composite cathode active materials. Accordingly, the high-rate characteristics of a lithium battery containing a composite cathode active material containing the second carbon-based material can be improved.
[0103] The aspect ratio of the second carbon-based material may be 10 or more, for example, 10 to 100,000, 10 to 80,000, 10 to 50,000, 10 to 10,000, 10 to 5000, 10 to 1000, 10 to 500, 10 to 100, or 10 to 50. The aspect ratio of the second carbon-based material is, for example, the ratio of the length of the major axis passing through the center of the second carbon-based material, i.e., the length of the second carbon-based material, and the length of the minor axis perpendicular to the major axis, i.e., the diameter of the second carbon-based material.
[0104] The diameter of the second carbon-based material may be, for example, 1 nm to 50 nm, 1 nm to 30 nm, or 1 nm to 10 nm. When the diameter of the second carbon-based material is within the above range, the absolute number of strands per volume is reduced, allowing for uniform dispersion without a negligible effect on reducing internal resistance.
[0105] The length of the second carbon-based material may be, for example, 100 nm to 1000 μm, 100 nm to 500 μm, 100 nm to 100 μm, 100 nm to 50 μm, 100 nm to 10 μm, 100 nm to 5 μm, 100 nm to 2 μm, 100 nm to 1 μm, 100 nm to 500 nm, or 100 nm to 300 nm. The length of the second carbon-based material may be, for example, 500 nm to 1000 μm, 500 nm to 500 μm, 500 nm to 100 μm, 500 nm to 50 μm, 500 nm to 10 μm, 500 nm to 5 μm, or 500 nm to 2 μm. When the length of the second carbon-based material is within the above range, an effective conductive path can be provided without a decrease in the internal resistance of the electrode.
[0106] The second carbon-based material may include, for example, carbon nanofibers, carbon nanotubes, or a combination thereof.
[0107] Carbon nanotubes may include, for example, a carbon nanotube primary structure, a carbon nanotube secondary structure formed by the aggregation of a plurality of carbon nanotube primary particles, or a combination thereof.
[0108] The carbon nanotube primary structure is a single carbon nanotube unit.
[0109] The carbon nanotube primary structure may include, for example, single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), and multi-walled carbon nanotubes (MWCNT), or a combination thereof. The diameter of the carbon nanotube primary structure may be, for example, 1 nm to 20 nm, 1 nm to 15 nm, or 2 nm to 10 nm. The length of the carbon nanotube primary structure may be, for example, 100 nm to 2 µm, 100 nm to 1 µm, 100 nm to 500 nm, 100 nm to 400 nm, 100 nm to 300 nm, or 200 nm to 300 nm. The diameter and length of the carbon nanotube primary structure can be measured using scanning electron microscope (SEM) images or laser diffraction.
[0110] A carbon nanotube secondary structure is a structure formed by assembling carbon nanotube primary structures to form a bundle or rope type, either wholly or partially. The carbon nanotube secondary structure may include, for example, bundle-type carbon nanotubes, rope-type carbon nanotubes, or a combination thereof. The diameter of the carbon nanotube secondary structure may be, for example, 2 nm or more or 3 nm or more. The diameter of the carbon nanotube secondary structure may be, for example, 50 nm or less, 30 nm or less, or 10 nm or less. The diameter of the carbon nanotube secondary structure may be, for example, 50 nm or less, 30 nm or less, or 10 nm or less. The diameter of the carbon nanotube secondary structure may be, for example, 2 nm to 50 nm, 2 nm to 30 nm, or 2 nm to 20 nm. The length of the carbon nanotube secondary structure may be, for example, 500 nm to 1000 μm, 500 nm to 500 μm, 500 nm to 200 μm, 500 nm to 100 μm, or 500 nm to 50 μm. The diameter and length of the carbon nanotube secondary structure can be measured using scanning electron microscope (SEM) images, an optical microscope, or laser diffraction. The carbon nanotube secondary structure can be converted into a carbon nanotube primary structure by dispersing it in, for example, a solvent, and then used to manufacture a dry cathode active material.
[0111] The content of the second carbon-based material may be, for example, 0.1 wt% to 50 wt%, 1 wt% to 40 wt%, or 5 wt% to 30 wt% with respect to the total weight of the first carbon-based material and the second carbon-based material. By including the first carbon-based material and the second carbon-based material within these ranges, a conduction path within the dry composite negative electrode active material is more effectively secured, thereby further reducing the internal resistance of the dry negative electrode active material. Consequently, the cycle characteristics of the lithium battery containing the dry negative electrode active material may be further improved. The content of the second carbon-based material may be, for example, 0.001 wt% to 5 wt%, 0.01 wt% to 3 wt%, or 0.01 wt% to 1 wt% with respect to the total weight of the dry negative electrode active material. By including a second carbon-based material within this range in the dry anode active material, a conduction path is secured within the composite anode active material, thereby further reducing the internal resistance of the dry anode active material. Consequently, the cycle characteristics of a lithium battery containing the dry anode active material can be further improved. The dry binder includes a fluorine-based binder, and the glass transition temperature (T) of the dry binder g The temperature is 15 to 100°C, and the dry binder content is 0.1 to 5 wt% with respect to the total weight of the dry cathode film. The specific surface area of the dry cathode active material is, for example, 1 m² 2 / g to 100 m 2 / g, 1 m 2 / g to 50 m 2 / g, or 1 m 2 / g to 30 m 2 / g. Since the composite negative electrode active material has a specific surface area within this range, the cycle characteristics of the lithium battery employing this composite negative electrode active material can be further improved. The average particle size (D50) of the composite negative electrode active material is, for example, 1 μm to 30 μm, 3 μm to 20 μm, or 5 μm to 15 μm. The particle size (D10) of the composite negative electrode active material is, for example, 0.1 μm to 10 μm, 0.5 μm to 10 μm, or 1 μm to 10 μm. The particle size (D90) of the composite negative electrode active material is, for example, 10 μm to 50 μm, 10 μm to 30 μm, or 10 μm to 25 μm. The cycle characteristics of a lithium battery employing such a dry cathode can be further improved by the composite cathode active material having an average particle size (D50), a particle size (D10), and / or a particle size (D90) within this range.
[0112] delete
[0113] The content of the dry conductive material included in the dry cathode film is, for example, 0.1 to 5 wt%, 0.5 to 5 wt%, or 1 to 5 wt% with respect to the total weight of the dry cathode film. By including the dry conductive material in this range, the conductivity of the dry cathode film is improved, and the cycle characteristics of the lithium battery including such a dry cathode film can be improved.
[0114] A dry cathode film is, for example, a self-standing film. A dry cathode film can maintain a film form without, for example, a support. Therefore, a dry cathode film can be prepared as a separate self-standing film and then placed on an electrode current collector. Since the dry cathode film is manufactured dry, it does not contain any intentionally added process solvents. For example, it does not contain residual processing solvents. Although trace amounts of unintended solvent may remain in the dry cathode film, these solvents are not intentionally added process solvents. Therefore, a dry cathode film is distinguished from a wet electrode film, which is manufactured by mixing the components with the process solvent and then removing some or all of the process solvent by drying.
[0115] In a dry cathode film according to one embodiment, the first dry cathode film comprises a mixture of a carbon-based material and a silicon-based active material as a core of a dry composite cathode active material; a composite of a carbon-based material and a silicon-based active material; or a combination thereof, and the second dry cathode film comprises a carbon-based material as a core of a dry composite cathode active material, wherein the content of the binder and the composite of the first dry cathode film is equal to or greater than the content of the binder and the composite of the second dry cathode film, respectively.
[0116] The above-mentioned second dry cathode film may further include a conductive material. The conductive material may include a composite (GB), Denka Black, Thermo Black, Super P, carbon nanotubes, activated carbon, carbon molecular sieve, graphene, carbon black, graphite microparticles, natural graphite, artificial graphite, acetylene black, Ketjen black, carbon fibers, carbon nanotubes; metal powders or metal fibers or metal tubes such as copper, nickel, aluminum, and silver; or conductive polymers such as polyphenylene derivatives. Here, the composite is identical to a composite comprising one or more first metal oxides and a first carbon-based material constituting the shell of a composite cathode active material, so a description thereof will be omitted.
[0117] The above dry cathode film comprises a first dry cathode film disposed adjacent to a cathode current collector and a second dry cathode film disposed on the first dry cathode film, wherein the first dry cathode film comprises a mixture of a carbon-based material and a silicon-based active material; a composite of a carbon-based material and a silicon-based active material; or a combination thereof as a core of a dry composite cathode active material, and the second dry cathode film comprises a mixture of a carbon-based compound and a silicon-based active material; a composite of a carbon-based compound and a silicon-based active material; or a combination thereof as a core of a dry cathode active material, wherein the content of the composite (GB) and binder of the first dry cathode film is equal to or greater than the content of the composite and binder of the second dry cathode film, and the content of the mixture of a carbon-based material and a silicon-based active material; the composite of a carbon-based material and a silicon-based active material; or the combination thereof in the first dry cathode film is equal to the content of the mixture of a carbon-based material and a silicon-based active material in the second dry cathode film; A composite of carbon-based materials and silicon-based active materials; or the content of the combination thereof is equal to or greater than that of the composite.
[0118] The first dry cathode film comprises a carbon-based material and a silicon-based active material as the core of the dry composite cathode active material, and the silicon-based active material comprises a silicon composite structure, and the second dry cathode film comprises a carbon-based material as the core of the dry composite cathode active material, and the content of the binder and the composite of the first dry cathode film is equal to or greater than the content of the binder and the composite of the second dry cathode film, respectively.
[0119] delete
[0120] The above dry cathode film comprises a first dry cathode film disposed adjacent to a cathode current collector and a second dry cathode film disposed on the first dry cathode film, wherein the first dry cathode film comprises a carbon-based material and a silicon-based active material as a core of a dry composite cathode active material, and the second dry cathode film comprises a carbon-based material and a silicon-based active material as a core of a dry cathode active material. Here, the silicon-based active material of the first dry cathode film and the second dry cathode film comprises a silicon composite structure. The content of the composite (GB) and binder of the first dry cathode film is equal to or greater than the content of the composite and binder of the second dry cathode film, and the content of the carbon-based material and silicon-based active material in the first dry cathode film is equal to or greater than the content of the carbon-based material and silicon-based active material in the second dry cathode film.
[0121] With reference to the attached drawings, the structure of a dry cathode-separator subassembly employing a dry cathode film according to one embodiment will be described.
[0122] Referring to FIG. 3a, the dry cathode-separator subassembly (200) has a structure in which a first dry cathode film (20a) is laminated on a cathode current collector (20), a second dry cathode film (20b) is laminated on top of the first dry cathode film (20a), and a separator (4) is laminated on top thereof.
[0123] The dry cathode-separator subassembly (200) shown in FIG. 3b differs from the case of FIG. 3a only in that an intermediate layer (30) is placed between the cathode current collector (20) and the first dry cathode film (20a).
[0124] FIGS. 4a to 4c show a stacked structure of a dry cathode according to one embodiment, and specifically show the composition of the first dry cathode and the second dry cathode.
[0125] According to one embodiment, as shown in FIG. 4a, the first dry cathode film (20a) comprises a composite cathode active material in which a shell containing a composite (GB1) is coated on graphite, which is a carbon-based material and is the first cathode active material, a silicon composite structure (SCN) which is the second cathode active material, and polytetrafluoroethylene (PTFE1) which is the dry binder. The second dry cathode film (20b) comprises a composite cathode active material in which a shell containing a composite (GB2) is coated on graphite, which is the first cathode active material, a silicon composite structure (SCN) which is the second cathode active material, and polytetrafluoroethylene (PTFE2) which is the dry binder.
[0126] The above silicon composite structure is a silicon-carbon composite comprising silicon particles and a first carbon-based material, a silicon-carbon composite comprising a core mixed with silicon particles and a second carbon-based material and a third carbon-based material surrounding the core, or a combination thereof.
[0127] The content of PTFE1 and GB1 of the first dry cathode film (20a) is controlled to be equal to or greater than the content of PTFE2 and GB2 of the second dry cathode film (20b), respectively (PTFE1 ≥ PTFE2, GB1 ≥ GB2). When within this range, the dry cathode film can be effectively prevented from peeling off from the cathode current collector, and lithium dendrite growth can be induced to be small away from the cathode current collector.
[0128] The weight ratio of PTFE1 and PTFE2 is not specifically limited, but is 10:1 to 1.1:1, 9.5:1 to 1.3:1, 9:1 to 1.5:1, 9:1 to 1.5:1, 6:1 to 1.5:1, 5:1 to 1.8:1, or 4:1 to 2:1.
[0129] The weight ratio of the mixture of GB1 and GB2 is not specifically limited, but is 10:1 to 1.1:1, 9.5:1 to 1.3:1, 9:1 to 1.5:1, 9:1 to 1.5:1, 6:1 to 1.5:1, 5:1 to 1.8:1, or 4:1 to 2:1.
[0130] The content of the silicon composite structure in the first dry cathode film and the second dry cathode film is 5 to 20 parts by weight, 11 to 18 parts by weight, or 12 to 15 parts by weight based on 100 parts by weight of the total content of graphite and silicon composite structure.
[0131] According to another embodiment, as shown in FIG. 4b, the first dry cathode film (20a) comprises a composite cathode active material having a shell containing a composite (GB1) coated on graphite, which is the first cathode active material, a silicon composite structure, which is the second cathode active material, and polytetrafluoroethylene (PTFE1), which is the dry binder. The second dry cathode film (20a) comprises a composite cathode active material having a shell containing a composite (GB2) coated on graphite, which is the first cathode active material, a silicon composite structure, which is the second cathode active material, and polytetrafluoroethylene (PTFE2), which is the dry binder.
[0132] The content of SCN1 in the first dry cathode film is controlled to be greater than the content of SCN2 in the second dry cathode film. When the content of SCN1 is controlled to be greater than the content of SCN2 in this way, the content of PTFE1 and GB1 in the first dry cathode film is controlled to be equal to or greater than the content of PTFE2 and GB2 in the second dry cathode film, respectively (SCN1 ≥ SCN2, PTFE1 ≥ PTFE2, GB1 ≥ GB2). In this range, volume expansion of the dry cathode film can be suppressed, and lithium dendrite growth can be induced to be small in the cathode film far from the current collector.
[0133] The mixed weight ratio of the content of SCN1 of the first dry cathode film and SCN2 of the second dry cathode film is not particularly limited, but is 10:1 to 1.1:1, 9.5:1 to 1.3:1, 9:1 to 1.5:1, 9:1 to 1.5:1, 6:1 to 1.5:1, 5:1 to 1.8:1, or 4:1 to 2:1.
[0134] When the silicon content of the first dry cathode film is greater than the silicon content of the second dry cathode film, the electrode expansion rate is reduced, dendrite formation during rapid charging is reduced, electrolyte penetration characteristics are improved, and electrode detachment is reduced, and higher electrode stability can be secured with less binder. In addition, if the content of PTFE1 and GB1 of the first dry cathode film is adjusted to be equal to or greater than the content of PTFE2 and GB2 of the second dry cathode film, respectively, the dry cathode film can be effectively prevented from peeling off from the cathode current collector, and lithium dendrite growth can be induced to be small away from the cathode current collector.
[0135] According to another embodiment, as shown in FIG. 4c, a second dry cathode film (20b) positioned far from the cathode current collector (20) comprises a first composite cathode active material containing a graphite core / composite (GB1) shell as a cathode active material and PTFE1 as a binder, and a first dry cathode film (20a) positioned adjacent to the cathode current collector (20) utilizes a first composite cathode active material coated with a shell containing a composite (GB1) on graphite as a dry composite cathode active material, a second composite cathode active material containing a silicon composite structure (SCN) as a core / composite (GB2) as a shell and PTFE2 as a binder.
[0136] The total content of the graphite and silicon composite structure (SCN) of the first dry cathode film can be significantly controlled compared to the graphite content of the second dry cathode film.
[0137] The total content of the graphite and silicon composite structure (SCN) of the first dry cathode film and the content of graphite of the second dry cathode film are not particularly limited, but the mixed weight ratio is 10:1 to 1.1:1, 9.5:1 to 1.3:1, 9:1 to 1.5:1, 9:1 to 1.5:1, 6:1 to 1.5:1, 5:1 to 1.8:1, or 4:1 to 2:1.
[0138] For example, in the first composite negative active material, the content of the composite (GB1) can be controlled to be greater than that of the composite (GB2), and the content of the binder PTFE1 can be controlled to be equal to or greater than that of the binder PTFE2 (PTFE1 ≥ PTFE2, GB1 ≥ GB2). By forming such a structure, control by volume expansion can be achieved, and a structure that induces small lithium dendrite growth at the far side of the current collector can be formed.
[0139] In FIG. 4b and FIG. 4c, the mixed weight ratio of PTFE1 and PTFE2 and the mixed weight ratio of GB1 and GB2 are as described in FIG. 4a.
[0140] The first dry cathode film and the second dry film of FIGS. 4a to 4c may further include a conductive material. For example, the second dry cathode film of FIG. 4c includes a first composite cathode active material containing a graphite core / composite (GB1) shell as a cathode active material and PTFE1 as a binder, and the second dry cathode film may further include a conductive material. The composite (GB), etc., may be used as the conductive material. Here, the composite is identical to the composite comprising one or more first metal oxides and a first carbon-based material constituting the shell of the composite cathode active material, so a description thereof will be omitted.
[0141] In a dry cathode including the dry cathode film described above, the first dry cathode film and
[0142] The thickness of the second dry cathode film can be formed in a ratio of 1:3 to 3:1, 1:2 to 2:1, or 1:1.
[0143] According to one embodiment, the dry cathode film has a multilayer structure of two or more layers, two to five layers, or two to three layers, and can form a thick film.
[0144] The above dry cathode film is a self-standing film, and the dry cathode film is free of residual processing solvent.
[0145] The tensile strength of the dry cathode film according to one embodiment may be, for example, 450 kPa or more, 500 kPa or more, 700 kPa or more, or 1000 kPa or more at 25°C. This tensile strength is for before rolling. The tensile strength of the dry cathode film before rolling may be, for example, 500 kPa to 5000 kPa, 600 kPa to 5000 kPa, 700 kPa to 5000 kPa, or 800 kPa to 5000 kPa at 25°C.
[0146] The tensile strength of the dry cathode film after rolling at 25°C may be 1000 kPa or more, 1050 kPa or more, 1200 kPa or more, or 1500 kPa or more. The tensile strength of the dry cathode film after rolling at 25°C may be, for example, 1000 kPa to 5000 kPa, 1050 kPa to 5000 kPa, 1090 kPa to 5000 kPa, 1200 kPa to 5000 kPa, or 1800 kPa to 5000 kPa. By having a tensile strength within the above-described range, the structural stability of the dry cathode film can be improved. Accordingly, the dry cathode film maintains a stable three-dimensional conductive network during the charge-discharge process, thereby improving the reversibility of the electrode reaction. The mechanical strength of the dry cathode film can be improved by the dry cathode film having a high tensile strength within this range. Since the dry cathode film has improved mechanical strength, local degradation due to volume change during charging and discharging of the electrode equipped with the dry cathode film and the lithium battery including it can be suppressed. As a result, the cycle characteristics of the lithium battery can be improved.
[0147] The dry cathode film includes the aforementioned dry cathode active material and provides improved cycle characteristics and reduced volume change.
[0148] A method for manufacturing a dry cathode comprises, for example, the step of preparing a dry mixture by dry mixing a dry composite cathode active material and a dry binder; the step of providing a cathode current collector; the step of placing an intermediate layer on one side of the cathode current collector; and the step of placing the dry mixture on the intermediate layer and rolling it to obtain a dry cathode film, thereby manufacturing a cathode having a cathode active material layer placed on one side of the cathode current collector.
[0149] First, a dry mixture is prepared by dry mixing a composite cathode active material and a dry binder.
[0150] When preparing a dry mixture, a dry conductive material may be further included.
[0151] Dry mixing refers to mixing without the use of a process solvent. A process solvent is, for example, a solvent used in the preparation of an electrode slurry. The process solvent is, for example, water, NMP, etc., but is not limited to these, and is not limited to any process solvent used in the preparation of an electrode slurry. Dry mixing can be performed using a stirrer at a temperature, for example, 25 to 65°C. Dry mixing can be performed using a stirrer at a rotational speed, for example, 10 to 10,000 rpm, or 100 to 10,000 rpm. Dry mixing can be performed using a stirrer for, for example, 1 to 200 minutes, or 1 to 150 minutes. The composite cathode active material is a dry composite cathode active material.
[0152] Dry mixing can be performed, for example, one or more times. First, a first mixture can be prepared by first dry mixing the dry composite cathode active material and the dry binder. A dry conductive material may be added when preparing the first mixture. The first dry mixing can be performed, for example, at a temperature of 25 to 65°C, at a rotational speed of 2000 rpm or less, or 500 to 2000 rpm, for a time of 15 minutes or less, for example, 5 to 15 minutes. By the first dry mixing, the dry composite cathode active material and the dry binder can be uniformly mixed. Subsequently, a second mixture can be prepared by second dry mixing the dry composite cathode active material and the dry binder. Secondary dry mixing can be performed, for example, at a temperature of 25 to 65 ℃ or 25 to 65 ℃, at a rotational speed of 4000 rpm or more or 4000 to 9000 rpm for 10 minutes or more, or 10 to 60 minutes. By secondary dry mixing, a dry mixture comprising a fibrillized dry binder can be obtained.
[0153] The stirrer is, for example, a kneader. The stirrer comprises, for example, a chamber; one or more rotating shafts disposed inside the chamber and rotating; and blades rotatably coupled to the rotating shafts and disposed along the longitudinal direction of the rotating shafts. The blades may be, for example, one or more selected from ribbon blades, sigma blades, jet (Z) blades, dispersion blades, and screw blades. By including the blades, the dry cathode composite active material, the dry conductive material, and the dry binder can be effectively mixed without a solvent to produce a dough-like mixture.
[0154] The prepared dry mixture can be fed into an extrusion device and extruded in the form of a sheet. The pressure during extrusion is, for example, 4 MPa to 100 MPa, or 10 MPa to 90 MPa. The obtained sheet-shaped extruded material is a dry cathode film used as a sheet for a cathode active material layer. By repeating this process, a dry cathode film having a multilayer structure can be easily manufactured.
[0155] Dry conductive materials include carbon black, graphite fine particles, natural graphite, synthetic graphite, acetylene black, Ketjen black, carbon fibers; carbon nanotubes; metal powders such as copper, nickel, aluminum, and silver, or metal fibers or metal tubes; and conductive polymers such as polyphenylene derivatives, but are not limited to these; any material used as a conductive material in the relevant technical field is acceptable. For example, the conductive material is a carbon-based conductive material. A dry conductive material is a conductive material that has not come into contact with a process solvent.
[0156] As a dry binder, vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), mixtures of the aforementioned polymers, styrene butadiene rubber-based polymers, etc. are used, but are not necessarily limited to these, and any that are used in the relevant technical field are acceptable. For example, the dry binder is polytetrafluoroethylene (PTFE). The dry binder is a binder that does not come into contact with the process solvent.
[0157] It is also possible to form pores inside the cathode active material layer by adding a plasticizer or a pore-forming agent to the dry mixture.
[0158] The content of the dry composite cathode active material, dry conductive material, and dry binder used in the cathode active material layer is used within the same range as in the case of wet cathode manufacturing. Next, a cathode current collector is provided.
[0159] Although not illustrated in the drawings, the negative current collector may comprise, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may comprise, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may comprise, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The polymer may be an insulating polymer. By including an insulating thermoplastic polymer in the base film, the base film may soften or liquefy upon the occurrence of a short circuit, thereby interrupting battery operation and suppressing a sudden increase in current. The metal layer may comprise, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), or an alloy thereof. The negative current collector may additionally comprise a metal piece and / or a lead tab. For more specific details regarding the base film, metal layer, metal chip, and lead tab of the negative electrode current collector, refer to the anode current collector described above. By having this structure, the negative electrode current collector can reduce the weight of the negative electrode and, consequently, improve the energy density of the negative electrode and the lithium battery.
[0160] The negative current collector is, for example, aluminum foil.
[0161] Next, an intermediate layer is disposed on at least one surface of the negative current collector. The intermediate layer may include a carbon-based conductive material and a binder. The intermediate layer may be omitted.
[0162] Next, a dry cathode film, which is a sheet for the cathode active material layer prepared on the intermediate layer, is placed and rolled to manufacture a cathode in which the cathode active material layer is disposed on one side of the cathode current collector. An intermediate layer is disposed between the cathode current collector and the cathode active material layer. Rolling may be performed using, for example, a roll press or a flat plate press, but is not necessarily limited to these. The pressure during rolling is, for example, 0.1 ton / cm² 2Up to 10.0 ton / cm 2 However, it is not limited to this range. If the pressure during rolling increases excessively, it may cause cracks in the cathode current collector. If the pressure during rolling is excessively low, the bonding strength between the cathode current collector and the cathode active material layer may decrease.
[0163] A lithium battery according to another embodiment employs a cathode comprising the dry cathode film described above.
[0164] By employing the aforementioned negative electrode, the lithium battery provides improved interfacial resistance, cycle characteristics, and reduced volume change.
[0165] Lithium batteries are manufactured, for example, by the following exemplary method, but are not necessarily limited to this method and are adjusted according to the required conditions.
[0166] First, a dry cathode is manufactured according to the cathode manufacturing method described above.
[0167] Next, a positive active material composition is prepared by mixing a positive active material, a conductive material, a binder, and a solvent. The positive active material composition is directly coated and dried onto a positive current collector to manufacture a positive plate. Alternatively, the positive active material composition may be cast onto a separate support, and then a film peeled from the support is laminated onto an aluminum current collector to manufacture a positive plate.
[0168] The cathode active material is a lithium-containing metal oxide, and any that is commonly used in the industry may be used without limitation. For example, one or more composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof may be used as the cathode active material. The cathode active material may include one or more selected from the group consisting of, for example, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate oxide, and lithium manganese oxide, but is not necessarily limited to these, and any that are used as cathode active materials for lithium batteries in the relevant technical field are possible.
[0169] The cathode active material is, for example, Li a A 1-b B b D2(wherein 0.90 ≤ a ≤ 1.8, and 0 ≤ b ≤ 0.5); Li a E 1-b B b O 2-c D c (In the above formula, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05); LiE 2-b B b O 4-c D c (In the above equation, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05); Li a Ni 1-b-c Co b B c D α (In the above equation, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α ≤ 2); Li a Ni 1-b-c Co b B c O 2-α F α (In the above equation, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2); Li a Ni 1-b-c Co b B c O 2-α F2(wherein, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2); Li a Ni 1-b-c Mn b B c D α (In the above equation, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α ≤ 2); Li a Ni 1-b-c Mn b B c O 2-α F α(In the above equation, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2); Li a Ni 1-b-c Mn b B c O 2-α F2(wherein, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.5, 0 ≤ c ≤ 0.05, 0 < α < 2); Li a Ni b E c G d O2(wherein 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0.001 ≤ d ≤ 0.1); Li a Ni b Co c Mn d GeO2(wherein the above formula, 0.90 ≤ a ≤ 1.8, 0 ≤ b ≤ 0.9, 0 ≤ c ≤ 0.5, 0 ≤ d ≤ 0.5, 0.001 ≤ e ≤ 0.1); Li a NiG b O2(in the above equation, 0.90 ≤ a ≤ 1.8, 0.001 ≤ b ≤ 0.1); Li a CoG b O2(in the above equation, 0.90 ≤ a ≤ 1.8, 0.001 ≤ b ≤ 0.1); Li a MnG b O2(in the above equation, 0.90 ≤ a ≤ 1.8, 0.001 ≤ b ≤ 0.1); Li a Mn2G b O4(wherein 0.90 ≤ a ≤ 1.8 and 0.001 ≤ b ≤ 0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiIO2; LiNiVO4; Li (3-f) J2(PO4)3(0 ≤ f ≤ 2); Li (3-f) It may include a compound represented by any one of the chemical formulas of Fe2(PO4)3 (0 ≤ f ≤ 2); and LiFePO4.
[0170] In the above-described chemical formula, A is Ni, Co, Mn, or a combination thereof; B is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D is O, F, S, P, or a combination thereof; E is Co, Mn, or a combination thereof; F is F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q is Ti, Mo, Mn, or a combination thereof; I is Cr, V, Fe, Sc, Y, or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof.
[0171] It is possible to use a compound having a coating layer added to the surface of the compound described above, and it is also possible to use a mixture of the compound described above and the compound having a coating layer added. The coating layer added to the surface of the compound described above includes, for example, a coating element compound of an oxide, hydroxide, oxyhydroxide, oxycarbonate, or hydroxycarbonate of a coating element. The compound forming such a coating layer is amorphous or crystalline. The coating elements included in the coating layer are Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or mixtures thereof. The method for forming the coating layer is selected within a range that does not adversely affect the physical properties of the cathode active material. The coating method is, for example, spray coating or immersion. Since the specific coating method is well understood by those skilled in the art, a detailed explanation will be omitted.
[0172] The cathode active material is, for example, LiNiO2, LiCoO2, LiMn x O 2x (x=1, 2), LiNi 1-x Mn x O2(0 <x<1), LiNi 1-x-y Co x Mn yO2 (0≤x≤0.5, 0≤y≤0.5), LiFeO2, V2O5, TiS, MoS, etc. can be used.
[0173] The cathode active material is, for example, Li a Ni x Co y M z O 2-b A b (1.0≤a≤1.2, 0≤b≤0.2, 0.8≤x<1, 0≤y≤0.3, 0 <z≤0.3, x+y+z=1, M은 망간(Mn), 니오븀(Nb), 바나듐(V), 마그네슘(Mg), 갈륨(Ga), 실리콘(Si), 텅스텐(W), 몰리브덴(Mo), 철(Fe), 크롬(Cr), 구리(Cu), 아연(Zn), 티타늄(Ti), 알루미늄(Al) 및 보론(B)으로 이루어진 군으로부터 선택된 하나 이상, A는 F, S, Cl, Br 또는 이들의 조합), LiNi x Co y Mn z O2(0.8≤x≤0.95, 0 <y≤0.2, 0<z≤0.2 및 x+y+z=1), LiNi x Co y Al z O2(0.8≤x≤0.95, 0≤y≤0.2, 0 <z≤0.2, x+y+z=1), LiNi x Co y Al v Mn w O2(0.8≤x≤0.95, 0≤y≤0.2, 0 <v≤0.2, 0<w≤0.2, x+y+v+w=1), Li a Ni x Mn y M' z O 2-b A b(1.0≤a≤1.2, 0≤b≤0.2, 0 <x≤0.3, 0.5≤y<1, 0<z≤0.3, 및 x+y+z=1, M'는 코발트(Co), 니오븀(Nb), 바나듐(V), 마그네슘(Mg), 갈륨(Ga), 실리콘(Si), 텅스텐(W), 몰리브덴(Mo), 철(Fe), 크롬(Cr), 구리(Cu), 아연(Zn), 티타늄(Ti), 알루미늄(Al), 보론(B) 또는 이들의 조합, A는 F, S, Cl, Br 또는 이들의 조합) 등이 사용될 수 있다.
[0174] In the positive electrode active material composition, the conductive material, binder, and solvent may be the same as those used in the negative electrode active material composition. Meanwhile, it is also possible to form pores inside the electrode plate by adding a plasticizer to the positive electrode active material composition and / or the negative electrode active material composition.
[0175] The content of the cathode active material, conductive material, binder, and solvent is at a level typically used in lithium batteries. Depending on the application and composition of the lithium battery, one or more of the conductive material, binder, and solvent may be omitted.
[0176] The binder content included in the anode may be, for example, 0.1 to 10 wt% or 0.1 to 5 wt% of the total weight of the anode active material layer. The conductive material content included in the anode may be, for example, 0.1 to 10 wt% or 0.1 to 5 wt% of the total weight of the anode active material layer. The anode active material content included in the anode may be, for example, 70 wt% to 99 wt%, 90 wt% to 99 wt%, or 95 wt% to 99 wt% of the total weight of the anode active material layer.
[0177] The positive current collector may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The metal layer may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. By having such a structure, the positive current collector can reduce the weight of the electrode and, consequently, improve the energy density of the lithium battery.
[0178] Next, a separator to be inserted between the positive and negative electrodes is prepared.
[0179] Any separator commonly used in lithium batteries is acceptable. For example, a separator is used that exhibits low resistance to electrolyte ion movement and excellent electrolyte wettability. The separator is selected from, for example, glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or combinations thereof, and is in the form of a nonwoven or woven fabric. For lithium-ion batteries, windable separators such as polyethylene or polypropylene are used, while for lithium-ion polymer batteries, separators with excellent organic electrolyte impregnation capabilities are used.
[0180] The separator is manufactured using the following exemplary method, but is not necessarily limited to this method and is adjusted according to the required conditions.
[0181] First, a separator composition is prepared by mixing a polymer resin, a filler, and a solvent. The separator composition is directly coated and dried on the electrode to form a separator. Alternatively, the separator composition is cast and dried on a support, and then a separator film peeled from the support is laminated onto the electrode to form a separator.
[0182] The polymer used in the manufacture of the separator is not particularly limited, and any polymer used as a binder for the electrode plate is acceptable. For example, vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, or mixtures thereof are used.
[0183] Next, the electrolyte is prepared.
[0184] The electrolyte is, for example, an organic electrolyte. An organic electrolyte is prepared, for example, by dissolving a lithium salt in an organic solvent.
[0185] Any organic solvent used as an organic solvent in the relevant technical field is acceptable. Examples of organic solvents include propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, sulfolane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or mixtures thereof.
[0186] Any lithium salt used as a lithium salt in the relevant technical field is also acceptable. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(FSO2)2N, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, and LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2)(1≤x≤20, 1≤y≤20), LiCl, LiI, or mixtures thereof.
[0187] Alternatively, the electrolyte is a solid electrolyte. The solid electrolyte is not limited to, for example, boron oxide, lithium oxynitride, etc., and any material used as a solid electrolyte in the relevant technical field is acceptable. The solid electrolyte is formed on the cathode, for example, by a method such as sputtering, or a separate solid electrolyte sheet is laminated on the cathode.
[0188] Solid electrolytes are, for example, oxide-based solid electrolytes or sulfide-based solid electrolytes.
[0189] Solid electrolytes are, for example, oxide-based solid electrolytes. Oxide-based solid electrolytes are Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 <x<2, 0≤y<3), BaTiO3, Pb(Zr,Ti)O3(PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT)(O≤x<1, O≤y<1), PB(Mg3Nb 2 / 3 )O3-PbTiO3(PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3(0 <x<2, 0<y<3), Lix Al y Ti z (PO4)3(0 <x<2, 0<y<1, 0<z<3), Li 1+x+y (Al, Ga) x (Ti, Ge) 2-x Si y P 3-y O 12 (0≤x≤1 0≤y≤1), Li x La y TiO3(0 <x<2, 0<y<3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2, Li 3+x La3M2O 12 It is one or more selected from (M = Te, Nb, or Zr, where x is an integer from 1 to 10). Solid electrolytes are produced by sintering methods, etc. For example, oxide-based solid electrolytes include Li7La3Zr2O 12 (LLZO) and Li 3+x La3Zr 2-a M a O 12 It is a garnet-type solid electrolyte selected from (M doped LLZO, M=Ga, W, Nb, Ta, or Al, x is an integer from 1 to 10).
[0190] Sulfide-based solid electrolytes may comprise, for example, lithium sulfide, silicon sulfide, phosphorus sulfide, boron sulfide, or combinations thereof. Sulfide-based solid electrolyte particles may comprise Li2S, P2S5, SiS2, GeS2, B2S3, or combinations thereof. Sulfide-based solid electrolyte particles may be Li2S or P2S5. Sulfide-based solid electrolyte particles are known to have high lithium ion conductivity compared to other inorganic compounds. For example, sulfide-based solid electrolytes comprise Li2S and P2S5. When the sulfide solid electrolyte material constituting the sulfide-based solid electrolyte comprises Li2S-P2S5, the mixed molar ratio of Li2S to P2S5 may be, for example, in the range of about 50:50 to about 90:10. Additionally, Li3PO4, halogens, halogen compounds, Li 2+2x Zn 1-x GeO4("LISICON", 0≤x<1), Li 3+y PO 4-x N x ("LIPON", 0 <x<4, 0<y<3), Li 3.25 Ge 0.25 P 0.75 S4("ThioLISICON"), Li2O-Al2O3-TiO2-P2O 5( Inorganic solid electrolytes prepared by adding "LATP" or similar materials to inorganic solid electrolytes of Li2S-P2S5, SiS2, GeS2, B2S3, or combinations thereof can be used as sulfide solid electrolytes. Non-limiting examples of sulfide solid electrolyte materials include Li2S-P2S5; Li2S-P2S5-LiX (X = halogen element); Li2S-P2S5-Li2O; Li2S-P2S5-Li2O-LiI; Li2S-SiS2; Li2S-SiS2-LiI; Li2S-SiS2-LiBr; Li2S-SiS2-LiCl; Li2S-SiS2-B2S3-LiI; Li2S-SiS2-P2S5-LiI; Li2S-B2S3; Li2S-P2S5-Z m S n(0 <m<10, 0<n<10, Z=Ge, Zn 또는 Ga); Li2S-GeS2; Li2S-SiS2-Li3PO4; 및 Li2S-SiS2-Li p MO q (0 <p<10, 0<q<10, M=P, Si, Ge, B, Al, Ga 또는 In)을 포함한다. 이와 관련하여, 황화물계 고체전해질 재료는 황화물계 고체전해질 물질의 원료 시작 물질(예를 들면, Li2S, P2S5, 등)을 용융 담금질법(melt quenching method), 기계적 밀링법 등에 의해 처리함으로써 제조될 수 있다. 또한, 소성(calcinations) 공정이 상기 처리 후에 수행될 수 있다. 황화물계 고체전해질은 비정질이거나, 결정질이거나, 이들이 혼합된 상태일 수 있다.
[0191] Referring to FIG. 5, a lithium battery (1) according to one embodiment includes a positive electrode (3), a negative electrode (2), and a separator (4). The positive electrode (3), the negative electrode (2), and the separator (4) are wound or folded to form a battery structure (7). The formed battery structure (7) is housed in a battery case (5). An organic electrolyte is injected into the battery case (5) and sealed with a cap assembly (6) to complete the lithium battery (1). The battery case (5) is cylindrical but is not necessarily limited to this shape and may be, for example, prismatic, thin film, etc.
[0192] Referring to FIG. 6, a lithium battery (1) according to one embodiment includes a positive electrode (3), a negative electrode (2), and a separator (4). A separator (4) is placed between the positive electrode (3) and the negative electrode (2), and the positive electrode (3), the negative electrode (2), and the separator (4) are wound or folded to form a battery structure (7). The formed battery structure (7) is housed in a battery case (5). It may include an electrode tab (8) that serves as an electrical path to guide the current formed in the battery structure (7) to the outside. An organic electrolyte is injected into the battery case (5) and sealed to complete the lithium battery (1). The battery case (5) is rectangular but is not necessarily limited to this shape and may be, for example, cylindrical, thin film, etc.
[0193] Referring to FIG. 7, a lithium battery (1) according to one embodiment includes a positive electrode (3), a negative electrode (2), and a separator (4). A separator (4) is placed between the positive electrode (3) and the negative electrode (2) to form a battery structure. The battery structure (7) is stacked in a bicell structure and then housed in a battery case (5). It may include an electrode tab (8) that serves as an electrical path to guide the current formed in the battery structure (7) to the outside. An organic electrolyte is injected into the battery case (5) and sealed to complete the lithium battery (1). The battery case (5) is rectangular but is not necessarily limited to this shape and may be, for example, cylindrical, thin film, etc.
[0194] The pouch-type lithium battery corresponds to the lithium batteries of FIGS. 5 to 7 in which a pouch is used as a battery case. The pouch-type lithium battery includes one or more battery structures. A separator is disposed between a positive electrode and a negative electrode to form a battery structure. The battery structure is stacked in a bicell structure, then impregnated with an organic electrolyte, and then housed and sealed in a pouch to complete the pouch-type lithium battery. For example, although not shown in the drawings, the aforementioned positive electrode, negative electrode, and separator are simply stacked to form an electrode assembly and housed in a pouch, or are wound into a jelly roll-shaped electrode assembly or folded and then housed in a pouch. Subsequently, an organic electrolyte is injected into the pouch and sealed to complete the lithium battery.
[0195] Lithium batteries are used in, for example, electric vehicles (EVs) due to their excellent lifespan and high-rate performance. For instance, they are used in hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs). Additionally, they are used in fields requiring large amounts of power storage, such as electric bicycles and power tools.
[0196] Multiple lithium batteries are stacked to form a battery module, and multiple battery modules form a battery pack. Such battery packs can be used in any device requiring high capacity and high output. For example, they can be used in laptops, smartphones, electric vehicles, etc. A battery module includes, for example, multiple batteries and a frame that holds them. A battery pack includes, for example, multiple battery modules and a bus bar connecting them. The battery modules and / or battery packs may further include a cooling device. Multiple battery packs are controlled by a battery management system. The battery management system includes a battery pack and a battery control device connected to the battery pack.
[0197] A dry cathode according to another embodiment comprises: an electrode current collector; and the above-described dry cathode film disposed on one or both sides of the electrode current collector.
[0198] By including a dry cathode film in the dry cathode, the internal resistance of the dry cathode is reduced and mechanical properties are improved.
[0199] The electrode current collector may include, for example, a substrate.
[0200] The material constituting the substrate may be any material that does not react with lithium, that is, a material that does not form an alloy or compound with lithium and possesses conductivity. The substrate may be, for example, a metal or an alloy. The substrate may be composed of, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel (SUS), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), or alloys thereof. The substrate may have a form selected from, for example, a sheet, foil, film, plate, porous body, mesoporous body, through-hole containing body, polygonal ring body, mesh body, foam, and nonwoven body, but is not necessarily limited to these forms and any form used in the relevant technical field is possible.
[0201] The electrode current collector may include, for example, a substrate; and an interlayer disposed between the substrate and the dry cathode film. The interlayer may include, for example, a carbon-based conductive material.
[0202] The interlayer is placed directly on, for example, one or both sides of the substrate. Therefore, no other layer may be placed between the substrate and the interlayer. By placing the interlayer directly on one or both sides of the substrate, the bonding strength between the substrate and the dry cathode film can be further improved.
[0203] The thickness of the intermediate layer is, for example, 0.01 to 30%, 0.1 to 30%, 0.5 to 30%, 1 to 25%, 1 to 20%, 1 to 15%, 1 to 10%, 1 to 5%, or 1 to 3% of the substrate thickness. The thickness of the intermediate layer is, for example, 10 nm to 5 µm, 50 nm to 5 µm, 200 nm to 4 µm, 500 nm to 3 µm, 500 nm to 2 µm, 500 nm to 1.5 µm, or 700 nm to 1.3 µm. By having the thickness of the intermediate layer within this range, the bonding strength between the substrate and the dry cathode film is further improved, and the increase in interfacial resistance is suppressed.
[0204] The intermediate layer includes, for example, a carbon-based conductive material. The carbon-based conductive material included in the intermediate layer may be selected from among carbon-based conductive materials used in dry cathode films. The intermediate layer may include the same carbon-based conductive material as that used in dry cathode films. By including a carbon-based conductive material, the intermediate layer may be, for example, a conductive layer.
[0205] The intermediate layer may additionally include a binder, for example. By additionally including a binder in the intermediate layer, the bonding strength between the substrate and the dry cathode film can be further improved. The binder included in the intermediate layer is, for example, a conductive binder or a non-conductive binder. The conductive binder is, for example, an ion-conducting binder and / or an electron-conducting binder. A binder having both ion conductivity and electron conductivity may belong to both ion-conducting binders and electron-conducting binders.
[0206] The binder included in the intermediate layer may be selected from binders used in dry cathode films. The intermediate layer may include the same binder as that used in dry cathode films. The binder included in the intermediate layer is, for example, a fluorine-based binder. The fluorine-based binder included in the intermediate layer is, for example, polyvinylidene fluoride (PVDF). The intermediate layer may be, for example, a binding layer containing a binder. The intermediate layer may be, for example, a conductive layer containing a binder and a carbon-based conductive material.
[0207] The intermediate layer may be disposed on a substrate in a dry or wet manner, for example. The intermediate layer may be disposed on a substrate in a dry manner by deposition such as CVD or PVD. The intermediate layer may be disposed on a substrate in a wet manner by spin coating, dip coating, for example. The intermediate layer may be disposed on a substrate by, for example, depositing a carbon-based conductive material on the substrate by deposition. The dry-coated intermediate layer may consist of a carbon-based conductive material and may not contain a binder. The intermediate layer may be disposed on a substrate by, for example, coating a composition comprising a carbon-based conductive material, a binder, and a solvent onto the surface of the substrate and drying it. The intermediate layer may have a single-layer structure or a multilayer structure comprising multiple layers, for example, a two-layer structure, a three-layer structure, or a four-layer structure.
[0208] The dry cathode film included in the dry cathode corresponds to the electrode active material layer.
[0209] The dry cathode includes a dry cathode film, and the dry cathode film includes a dry cathode active material having the core / shell structure described above.
[0210] A dry cathode active material having the above-described core / shell structure comprises, in the core, a carbon-based material; a mixture of a carbon-based material and a silicon-based active material; a composite of a carbon-based material and a silicon-based active material; or a combination thereof, and comprises in the shell a first metal oxide and a first carbon-based material.
[0211] The dry cathode active material may additionally include conventional general dry cathode active materials in addition to the dry cathode active material having the core / shell structure described above. Any conventional dry cathode active material commonly used in the industry may be used without limitation.
[0212] Any dry negative electrode active material used as a negative electrode active material for a lithium battery in the relevant technical field is acceptable. For example, it includes one or more selected from the group consisting of lithium metal, metals alloyable with lithium, transition metal oxides, non-transition metal oxides, and carbon-based materials. Metals alloyable with lithium include, for example, Si, Sn, Al, Ge, Pb, Bi, Sb Si-Y alloy (wherein Y is an alkali metal, alkaline earth metal, group 13 element, group 14 element, transition metal, rare earth element, or a combination thereof, and is not Si), Sn-Y alloy (wherein Y is an alkali metal, alkaline earth metal, group 13 element, group 14 element, transition metal, rare earth element, or a combination thereof, and is not Sn), etc. Element Y is, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof. Transition metal oxides are, for example, lithium titanium oxide, vanadium oxide, lithium vanadium oxide, etc. Non-transition metal oxides are, for example, SnO2, SiO2 x(0 <x<2) 등이다. 탄소계 재료는 예를 들어 결정질 탄소, 비정질 탄소 또는 이들의 혼합물이다. 결정질 탄소는 예를 들어 무정형, 판상, 린편상(flake), 구형 또는 섬유형의 천연 그래파이트 또는 인조 그래파이트와 같은 그래파이트다. 비정질 탄소는 예를 들어 소프트 카본(soft carbon: 저온 소성 탄소) 또는 하드 카본(hard carbon), 메조페이스 피치(mesophase pitch) 탄화물, 소성된 코크스 등이다.
[0213] For example, one or more composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof can be used as the positive electrode active material, and specific examples are as described above.
[0214] A dry cathode is, for example, a dry cathode. The dry cathode includes a dry cathode film, and the dry cathode film includes a dry cathode active material.
[0215] According to another embodiment, a lithium battery comprises a first electrode; a second electrode; and an electrolyte disposed between the first electrode and the second electrode, wherein the first electrode, the second electrode, or a combination thereof is the dry negative electrode described above.
[0216] The cycle characteristics of a lithium battery are improved by having a dry negative electrode having reduced internal resistance and improved mechanical properties.
[0217] A lithium battery may include, for example, a dry negative electrode, or a dry negative electrode and a dry positive electrode. A lithium battery may include, for example, a dry negative electrode and a wet positive electrode, or a dry positive electrode and a dry negative electrode.
[0218] A lithium battery includes an electrolyte, and the electrolyte may include, for example, a liquid electrolyte, a solid electrolyte, or a combination thereof.
[0219] Liquid electrolytes are, for example, organic electrolytes. Organic electrolytes are, for example, prepared by dissolving a lithium salt in an organic solvent.
[0220] Any organic solvent used as an organic solvent in the relevant technical field is acceptable. Examples of organic solvents include propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, sulfolane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or mixtures thereof.
[0221] Any lithium salt used as a lithium salt in the relevant technical field is also acceptable. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, and LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2)(where x and y are natural numbers), LiCl, LiI, or mixtures thereof, etc.
[0222] Solid electrolytes may include, for example, inorganic solid electrolytes, organic solid electrolytes, organic-inorganic composite solid electrolytes, or combinations thereof.
[0223] Solid electrolytes may include, for example, oxide-based solid electrolytes, sulfide-based solid electrolytes, polymer-based solid electrolytes, or combinations thereof.
[0224] The solid electrolyte is not limited to, for example, boron oxide, lithium oxynitride, etc., and any material used as a solid electrolyte in the relevant technical field is acceptable. The solid electrolyte is formed on the cathode, for example, by a method such as sputtering, or a separate solid electrolyte sheet is laminated on the cathode.
[0225] Oxide-based solid electrolytes are, for example, Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 <x<2, 0≤y<3), BaTiO3, Pb(Zr,Ti)O3(PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT, 0≤x<1, 0≤y<1), PB(Mg3Nb 2 / 3 )O3-PbTiO3(PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3(0 <x<2, 0<y<3), Li x Al y Ti z (PO4)3(0 <x<2, 0<y<1, 0<z<3), Li 1+x+y (Al, Ga) x (Ti, Ge) 2-x Si y P 3-y O 12 (0≤x≤1 0≤y≤1), Li x La y TiO3(0 <x<2, 0<y<3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2, Li 3+x La3M2O 12 (M = Te, Nb, or Zr, 0≤x≤10), Li 3+x La3Zr 2-y My O 12 (M-doped LLZO, M=Ga, W, Nb, Ta, Al or a combination thereof, 0≤x≤10, 0 <y<2), Li7La3Zr 2-x Ta x O 12 (0 <x<2, LLZ-Ta), 또는 이들의 조합을 포함한다. 산화물계 고체전해질은 예를 들어 가넷계(Garnet-type) 고체전해질이다. 산화물계 고체전해질은 소결법 등에 의하여 제작된다.
[0226] Oxide-based solid electrolytes are, for example, Li7La3Zr2O 12 (LLZO), Li 6.5 La3Zr 1.5 Ta 0.5 O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 0.34 La 0.51 TiO 2.94 , Li 1.07 Al 0.69 Ti 1.46 (PO4)3, 50Li4SiO4-50Li2BO3, 90Li3BO3-10Li2SO4, Li 2.9 PO 3.3 N 0.46 , or a combination thereof.
[0227] Sulfide-based solid electrolytes are, for example, Li2S-P2S5, Li2S-P2S5-LiX, where X is a halogen element, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n , m, n are positive numbers, Z is one of Ge, Zn, or Ga, Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MOq , p, q are positive numbers, M is one of P, Si, Ge, B, Al, Ga, In, Li 7-x PS 6-x Cl x , 0≤x≤2, Li 7-x PS 6-x Br x , 0≤x≤2, and Li 7-x PS 6-x I x It is one or more selected from , 0≤x≤2. Sulfide-based solid electrolytes are produced by processing starting materials, such as Li2S, P2S5, etc., by methods such as melt quenching or mechanical milling. Additionally, heat treatment may be performed after such processing. Sulfide-based solid electrolytes may be amorphous, crystalline, or a mixture thereof.
[0228] Sulfide-based solid electrolytes may include, for example, an argyrodite-type solid electrolyte represented by the following chemical formula 9:
[0229] <Chemical Formula 9>
[0230] Li + 12-n-x A n+ X 2- 6-x Y - x
[0231] In the above formula, A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb, or Ta, X is S, Se, or Te, Y is Cl, Br, I, F, CN, OCN, SCN, or N3, and 1(n(5, 0(x(2).
[0232] Sulfide-based solid electrolytes are Li 7-x PS 6-x Cl x , 0≤x≤2, Li 7-x PS 6-x Br x , 0≤x≤2, and Li 7-x PS 6-xI x It may be an argyrodite-type compound containing one or more selected from 0≤x≤2. In particular, the sulfide-based solid electrolyte included in the solid electrolyte may be an argyrodite-type compound containing one or more selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I.
[0233] Polymer-based solid electrolytes may be, for example, solid electrolytes comprising an ion-conducting polymer and a lithium salt, solid electrolytes comprising an ionic liquid polymer and a lithium salt, or combinations thereof.7
[0234] An ion-conducting polymer is a polymer that includes an ion-conducting repeating unit in its main chain or side chain. The ion-conducting repeating unit is a unit having ion conductivity and may be, for example, an alkylene oxide unit, a hydrophilic unit, etc. The ion-conducting polymer may include, for example, ether-based monomers, acrylic-based monomers, methacrylic-based monomers, siloxane-based monomers, or a combination thereof as a conductive repeating unit. The ion-conducting polymer may be, for example, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyethyl methacrylate, polydimethylsiloxane, polyacrylic acid, polymethacrylic acid, polymethyl acrylate, polyethyl acrylate, poly2-ethylhexyl acrylate, polybutyl methacrylate, poly2-ethylhexyl methacrylate, polydecyl acrylate, polyethylene vinyl acetate, or a combination thereof. Ion-conducting polymers may be, for example, polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyvinylsulfone, or a combination thereof.
[0235] A polymeric ionic liquid (PIL) comprises, for example, i) one or more cations selected from ammonium-based, pyrrolidinium-based, pyridinium-based, pyrimidinium-based, imidazolium-based, piperidinium-based, pyrazolium-based, oxazolium-based, pyridazinium-based, phosphonium-based, sulfonium-based, triazole-based, and mixtures thereof, and ii) BF4-, PF6-, AsF6-, SbF6-, AlCl4-, HSO4-, ClO4-, CH3SO3-, CF3CO2-, (CF3SO2)2N-, Cl-, Br-, I-, SO4 - , CF3SO3-, (C2F5SO2)2N-, (C2F5SO2)(CF3SO2)N-, NO3 - , Al2Cl7 - , CH3COO - , CF3SO3 - , (CF3SO2)3C - , (CF3CF2SO2)2N - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , SF5CF2SO3 - , SF5CHFCF2SO3 - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (O(CF3)2C2(CF3)2O)2PO -It may contain repeating units comprising one or more anions selected from and (CF3SO2)2N-. The ionic liquid polymer may be, for example, poly(diallyldimethylammonium)TFSI, poly(1-allyl-3-methylimidazolium trifluoromethanesulfonylimide), poly((N-methyl-N-propylpiperidinium bis(trifluoromethanesulfonyl)imide)), or a combination thereof.
[0236] Lithium salts include, for example, LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 It may be SO2)(1≤x≤20, 1≤y≤20), LiCl, LiI, or a combination thereof.
[0237] A method for manufacturing a dry cathode according to another embodiment is provided.
[0238] A method for manufacturing a dry cathode comprises the steps of: providing a dry cathode film; and placing an electrochemical electrode film on one or both sides of an electrode current collector.
[0239] The step of providing a dry cathode film includes: a step of preparing a dry mixture by dry mixing a dry cathode active material and a dry binder; and a step of preparing a dry cathode film by molding the dry mixture.
[0240] First, a dry mixture is prepared by dry mixing a negative electrode active material and a dry binder. For example, a dry mixture is prepared by dry mixing a dry negative electrode active material and a dry binder.
[0241] The above dry mixture may further include a dry conductive material.
[0242] Dry mixing means mixing without the use of a process solvent. A process solvent is, for example, a solvent used in the preparation of an electrode slurry. The process solvent is, for example, water, NMP, etc., but is not limited to these, and is not limited to any process solvent used in the preparation of an electrode slurry. Dry mixing can be performed using a stirrer at a rotational speed of 10 to 10,000 rpm at a temperature of, for example, 15 °C to 65 °C. Dry mixing can be performed using a stirrer for, for example, 1 to 200 minutes.
[0243] Dry mixing can be performed, for example, one or more times. First, a first dry mixture can be prepared by first dry mixing a dry cathode active material, a dry conductive material, and a dry binder. The first dry mixing can be performed, for example, at a temperature of 25 to 65°C, at a rotational speed of 10 to 2000 rpm or less, for a time of 15 minutes or less. Subsequently, a second mixture can be prepared by additionally dry mixing the first dry mixture. The second dry mixing can be performed, for example, at a temperature of 25 to 65°C, at a rotational speed of 3000 to 9000 rpm, for 10 to 60 minutes. A dry mixture comprising a fibrillized dry binder can be obtained by the second dry mixing.
[0244] The stirrer is, for example, a kneader. The stirrer comprises, for example, a chamber; one or more rotating shafts disposed inside the chamber and rotating; and blades rotatably coupled to the rotating shafts and disposed along the longitudinal direction of the rotating shafts. The blades may be, for example, one or more selected from ribbon blades, sigma blades, jet (Z) blades, dispersion blades, and screw blades. By including the blades, the electrode active material, dry conductive material, and dry binder can be effectively mixed without a solvent to produce a dough-like mixture.
[0245] Dry binders used include, for example, vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), mixtures of the aforementioned polymers, styrene butadiene rubber-based polymers, etc. The dry binder can be selected from among the dry binders used in the dry cathode film described above.
[0246] Dry conductive materials may be, for example, carbon black, graphite fine particles, natural graphite, synthetic graphite, acetylene black, Ketjen black, carbon fibers; carbon nanotubes; metal powders such as copper, nickel, aluminum, and silver, or metal fibers or metal tubes; conductive polymers such as polyphenylene derivatives, but are not limited to these, and any material used as a conductive material in the relevant technical field is acceptable. The conductive material is, for example, a carbon-based conductive material. The dry conductive material may be selected from among the dry conductive materials used in the dry cathode film described above.
[0247] It is also possible to form pores inside the electrode plate by adding a plasticizer or a pore-forming agent to the dry mixture.
[0248] The content of the dry cathode active material, dry binder, and dry conductive material used in the dry cathode film is at a level typically used in lithium batteries.
[0249] The dry anode film uses a dry anode active material as the dry cathode active material. The dry anode active material refers to the dry cathode film described above. The dry cathode film uses a dry cathode active material as the dry cathode active material. The dry cathode active material refers to the dry cathode film described above.
[0250] Next, a dry mixture is molded to prepare a dry cathode film.
[0251] The manufactured dry mixture can be fed into an extrusion device and extruded in the form of a sheet or film. The pressure during extrusion is, for example, 4 MPa to 100 MPa.
[0252] Next, an electrode current collector having an intermediate layer disposed on one or both sides of a substrate is provided.
[0253] The step of providing an electrode current collector having an intermediate layer disposed on one or both sides of a substrate comprises, for example, a step of providing a substrate; and a step of disposing of an intermediate layer on one or both sides of the substrate.
[0254] For the electrode current collector, refer to the electrode current collector section described above. The substrate of the positive current collector is, for example, aluminum foil. The substrate of the negative current collector is, for example, copper foil.
[0255] The step of placing an intermediate layer on one or both sides of a substrate includes dry coating and / or wet coating. Dry coating involves, for example, coating a carbon-based conductive material and / or its precursor onto one or both sides of an electrode current collector by deposition or the like. Deposition is performed at a temperature ranging from room temperature to high temperature and at a pressure ranging from atmospheric pressure to vacuum. The intermediate layer placed by dry coating may be made of a carbon-based material and may not contain a binder. Wet coating involves, for example, coating a composition comprising a carbon-based conductive material and a binder onto one or both sides of an electrode current collector. The composition comprises, for example, a carbon-based conductive material, a binder, and a process solvent. Refer to the electrode portion described above regarding the carbon-based conductive material and the binder. The process solvent may be selected from solvents used in the preparation of the electrode slurry. The process solvent is removed by drying after the composition is coated onto the electrode current collector. The coating method is not limited to spin coating, dip coating, etc., and any coating method used in the relevant art field is possible.
[0256] Next, the dry cathode film is placed simultaneously or sequentially on one or both sides of the electrode current collector to manufacture a dry cathode.
[0257] A rolling step may be added while and / or after placing a dry cathode film on one or both sides of an electrode current collector.
[0258] Rolling may be, for example, a roll press, a flat plate press, etc., but is not necessarily limited to these. The pressure during rolling is, for example, 1.0 to 10.0 ton / cm. If the pressure during rolling increases excessively, it may cause cracking of the electrode current collector. If the pressure during rolling is excessively low, the bonding strength between the electrode current collector and the dry cathode film may decrease.
[0259] Lithium batteries are manufactured, for example, by the following exemplary methods, but are not necessarily limited to these methods and vary depending on the required conditions.
[0260] First, one or both of the anode and the cathode may be manufactured according to the above-described dry cathode manufacturing method. Alternatively, if one of the anode and the cathode is manufactured by the above-described electrode manufacturing method, the other electrode may be manufactured by a wet manufacturing method. For example, the other electrode may be manufactured by preparing an electrode slurry comprising an electrode active material, a conductive material, a binder, and a solvent, coating the prepared electrode slurry onto an electrode current collector, and drying it. The conductive material and binder included in the electrode manufactured by the wet method may be selected from the conductive material and binder used in the above-described dry cathode manufacturing method.
[0261] Next, a separator to be inserted between the positive and negative electrodes is prepared.
[0262] The step of providing a dry cathode film comprises: a step of preparing a dry mixture by dry mixing a dry cathode active material and a dry binder as described above; and a step of preparing a dry cathode film by molding the dry mixture.
[0263] The dry cathode active material can be formed during the process of dry mixing the core and the composite.
[0264] The above composite comprises one or more first metal oxides; and a first carbon-based material, wherein the first metal oxide is disposed within a matrix of the first carbon-based material, and the first metal oxide has the formula M a O b (0 <a≤3, 0<b<4, a가 1, 2, 또는 3 이면, b는 정수가 아님)로 표시되며, 상기 M은 원소주기율표 2족 내지 16족 중에서 선택된 하나 이상의 금속이다.
[0265] The step of providing a composite includes, for example, supplying a reaction gas consisting of a carbon source gas to a structure including a metal oxide and heat-treating to provide a composite. The step of providing a composite is, for example, M a O c(0 <a≤3, 0<c≤4, a가 1, 2 또는 3인 경우, b가 정수임)로 표시되는 1 종 이상의 제2 금속산화물에 탄소 공급원 기체로 이루어진 반응 가스를 공급하고 열처리하여 복합체를 제조하는 단계를 포함하며, 상기 M은 원소주기율표 제2 족 내지 제13 족, 제15 족 및 제16 족 중에서 선택된 하나 이상의 금속이다.
[0266] The carbon source gas is a gas composed of a compound represented by the following chemical formula 10, or one or more mixed gases selected from the group consisting of a compound represented by the following chemical formula 10, a compound represented by the following chemical formula 11, and an oxygen-containing gas represented by the following chemical formula 12.
[0267] <Chemical Formula 10>
[0268] C n H (2n+2-a) [OH] a
[0269] In the above chemical formula 10, n is 1 to 20, and a is 0 or 1;
[0270] <Chemical Formula 11>
[0271] C n H 2n
[0272] In the above chemical formula 11, n is 2 to 6;
[0273] <Chemical Formula 12>
[0274] C x H y O z
[0275] In the above chemical formula 12, x is an integer of 0 or 1 to 20, y is an integer of 0 or 1 to 20, and z is 1 or 2.
[0276] The compound represented by Chemical Formula 10 and the compound represented by Chemical Formula 11 are one or more selected from the group consisting of methane, ethylene, propylene, methanol, ethanol, and propanol. The oxygen-containing gas represented by Chemical Formula 12 includes, for example, carbon dioxide (CO2) and carbon monoxide (CO), water vapor (H2O), or a mixture thereof.
[0277] M a O c (0 <a≤3, 0<c≤4, a가 1, 2, 또는 3이면, c는 정수임)로 표시되는 제2 금속산화물에 탄소 공급원 기체로 이루어진 반응 가스를 공급하고 열처리하는 단계 이후에 질소, 헬륨 및 아르곤으로 이루어진 군으로부터 선택된 하나 이상의 불활성 기체를 이용한 냉각 단계를 더 거칠 수 있다. 냉각 단계는 상온(20-25℃)으로 조절하는 단계를 말한다. 탄소 공급원 기체는 질소, 헬륨, 아르곤으로 이루어진 군으로부터 선택된 하나 이상의 불활성 기체를 포함할 수 있다.
[0278] In the method for manufacturing composites, the process of growing carbon-based materials, such as graphene, according to a gas-phase reaction can be carried out under various conditions.
[0279] According to the first condition, for example, M a O c (0 <a≤3, 0<c≤4, a가 1, 2, 또는 3이면, c는 정수임)로 표시되는 제2 금속산화물이 배치된 반응기에 먼저 메탄을 공급하고 열처리온도(T)까지 승온처리한다. 열처리 온도(T)까지의 승온 시간은 10 분 내지 4 시간이고 열처리온도(T)는 700 ℃ 내지 1100 ℃ 범위이다. 열처리온도(T)에서 반응 시간 동안 열처리를 실시한다. 반응시간은 예를 들어 4 시간 내지 8 시간이다. 열처리된 결과물을 상온으로 냉각시켜 복합체를 제조한다. 열처리온도(T)에서 상온까지 냉각하는 과정에 걸치는 시간은 예를 들어 1 시간 내지 5 시간이다.
[0280] According to the second condition, for example, Ma O c (0 <a≤3, 0<c≤4, a가 1, 2, 또는 3이면, c는 정수임)로 표시되는 제2 금속산화물이 배치된 반응기에 먼저 수소를 공급하고 열처리온도(T)까지 승온 처리한다. 열처리 온도(T)까지의 승온 시간은 10 분 내지 4 시간이고 열처리온도(T)는 700 ℃ 내지 1100 ℃ 범위이다. 열처리온도(T)에서 일정 반응 시간 동안 열처리한 후 메탄 가스를 공급하고 잔여 반응 시간 동안 열처리를 실시한다. 반응시간은 예를 들어 4 시간 내지 8 시간이다. 열처리된 결과물을 상온으로 냉각시켜 복합체를 제조한다. 냉각하는 과정에서 질소를 공급한다. 열처리온도(T)에서 상온까지 냉각하는 과정에 걸치는 시간은 예를 들어 1 시간 내지 5 시간이다.
[0281] According to the third condition, for example, M a O c (0 <a≤3, 0<c≤4, a가 1, 2, 또는 3이면, c는 정수임)로 표시되는 제2 금속산화물이 배치된 반응기에 먼저 수소를 공급하고 열처리온도(T)까지 승온 처리한다. 열처리 온도(T)까지의 승온 시간은 10 분 내지 4 시간이고 열처리온도(T)는 700 ℃ 내지 1100 ℃ 범위이다. 열처리온도(T)에서 일정 반응 시간 동안 열처리한 후 메탄과 수소의 혼합 가스를 공급하고 잔여 반응 시간 동안 열처리를 실시한다. 반응시간은 예를 들어 4 시간 내지 8 시간이다. 열처리된 결과물을 상온으로 냉각시켜 복합체를 제조한다. 냉각하는 과정에서 질소를 공급한다. 열처리온도(T)에서 상온까지 냉각하는 과정에 걸치는 시간은 예를 들어 1 시간 내지 5 시간이다.
[0282] In the process of manufacturing the composite, if the carbon source gas contains water vapor, a composite having excellent conductivity can be obtained. The content of water vapor in the gas mixture is not limited and, for example, is 0.01 volume% to 10 volume% based on 100 volume% of the total carbon source gas. The carbon source gas is, for example, methane; a mixed gas containing methane and an inert gas; or a mixed gas containing methane and an oxygen-containing gas.
[0283] The carbon source gas may be, for example, methane; a mixed gas of methane and carbon dioxide; or a mixed gas of methane, carbon dioxide, and water vapor. In the mixed gas of methane and carbon dioxide, the molar ratio of methane to carbon dioxide is about 1:0.20 to 1:0.50, about 1:0.25 to 1:0.45, or about 1:0.30 to 1:0.40. In the mixed gas of methane, carbon dioxide, and water vapor, the molar ratio of methane, carbon dioxide, and water vapor is about 1:0.20 to 0.50:0.01 to 1.45, about 1:0.25 to 0.45:0.10 to 1.35, or about 1:0.30 to 0.40:0.50 to 1.0.
[0284] The carbon source gas is, for example, carbon monoxide or carbon dioxide. The carbon source gas is, for example, a mixture of methane and nitrogen. In the mixture of methane and nitrogen, the molar ratio of methane to nitrogen is about 1:0.20 to 1:0.50, about 1:0.25 to 1:0.45, or about 1:0.30 to 1:0.40. The carbon source gas may not contain an inert gas such as nitrogen.
[0285] The heat treatment pressure can be selected by considering the heat treatment temperature, the composition of the gas mixture, and the desired amount of carbon coating. The heat treatment pressure can be controlled by adjusting the amount of the incoming gas mixture and the amount of the outgoing gas mixture. The heat treatment pressure is, for example, 0.5 atm or more, 1 atm or more, 2 atm or more, 3 atm or more, 4 atm or more, or 5 atm or more. The heat treatment pressure is, for example, 0.5 atm to 10 atm, 1 atm to 10 atm, 2 atm to 10 atm, 3 atm to 10 atm, 4 atm to 10 atm, or 5 atm to 10 atm.
[0286] The heat treatment time is not specifically limited and can be appropriately adjusted according to the heat treatment temperature, pressure during heat treatment, composition of the gas mixture, and the desired amount of carbon coating. For example, the reaction time at the heat treatment temperature is, for example, 10 minutes to 100 hours, 30 minutes to 90 hours, or 50 minutes to 40 hours. For example, as the heat treatment time increases, the amount of deposited carbon, for example, graphene (carbon), increases, and accordingly, the electrical properties of the composite may be improved. However, this trend may not necessarily be directly proportional to time. For example, after a predetermined period of time, carbon deposition, for example, graphene deposition, may no longer occur or the deposition rate may decrease.
[0287] Through the gas phase reaction of the aforementioned carbon source gas, M even at a relatively low temperature a O c (0 <a≤3, 0<c≤4, a가 1, 2, 또는 3이면, c는 정수임)로 표시되는 제2 금속산화물 및 그 환원 생성물인 M a O b(0 <a≤3, 0<b<4, a는 1, 2, 또는 3이며, b 는 정수가 아님)로 표시되는 제1 금속산화물 중에서 선택된 하나 이상에 균일한 탄소계 재료의 코팅 예를 들어 그래핀 코팅을 제공함에 의하여 복합체가 얻어진다.
[0288] The composite comprises a matrix of a carbon-based material having one or more structures selected from, for example, a spherical structure, a spiral structure in which multiple spherical structures are connected, a cluster structure in which multiple spherical structures are aggregated, and a sponge structure, for example, a graphene matrix, and M disposed within the graphene matrix. a O b (0 <a≤3, 0<b<4, a는 1, 2, 또는 3이며, b 는 정수가 아님)로 표시되는 제1 금속산화물 및 M a O c (0 <a≤3, 0<c≤4, a가 1, 2, 또는 3이면, c는 정수임)로 표시되는 제2 금속산화물 중에서 선택된 하나 이상을 포함한다.
[0289] The content of the dry binder is 1 to 10 weight%, 1 to 5 weight%, or 1.5 to 3.5 weight%, or 1.5 to 3 weight%, based on 100 weight% of the total content of the core, composite, and dry binder.
[0290] The present invention is explained in more detail through the following examples and comparative examples. However, the examples are intended to illustrate the present invention and do not limit the scope of the present invention.
[0291] (Manufacturing of composites)
[0292] Preparation Example 1: Al 2 O 3 @Gr complex
[0293] Al2O3 particles (average particle size: about 20 nm) were placed in the reactor, and then CH4 was supplied into the reactor at about 300 sccm and 1 atm for about 30 minutes, and the internal temperature of the reactor was raised to 1000 ℃ at a heating rate of about 23 ℃ / min.
[0294] Subsequently, heat treatment was performed by maintaining the above temperature for 7 hours. Then, the supply of CH4 was stopped, and the internal temperature of the reactor was adjusted to room temperature (25℃) to [prepare] Al2O3 particles and their reduction product, Al2O z (0 <z<3) 입자가 그래핀에 매립된 복합체를 얻었다.
[0295] The alumina content of the complex was 60 wt%.
[0296] Preparation Example 2: Al 2 O 3 @Gr complex
[0297] A composite was prepared in the same manner as in Preparation Example 1, except that Al2O3 particles (average particle size: about 200 nm) were used instead of Al2O3 particles (average particle size: about 20 nm).
[0298] Preparation Example 3: SiO 2 @Gr complex
[0299] SiO2 particles (average particle size: about 15 nm) were placed in the reactor, and then CH4 was supplied into the reactor at about 300 sccm at 1 atm for about 30 minutes, and the internal temperature of the reactor was raised to 1000℃.
[0300] Subsequently, heat treatment was performed by maintaining the above temperature for 7 hours. Then, the internal temperature of the reactor was adjusted to room temperature (20-25℃) to [treat] the SiO2 particles and their reduction product, SiO₂ y (0 <y<2) 입자가 그래핀에 매립된 복합체를 얻었다.
[0301] (Manufacturing of silicon-based cathode active materials)
[0302] Preparation Example 4
[0303] Flake graphite (SFG6) (Timcal, AG) (particle size: 4㎛, specific surface area: 17 m2 / g), pitch, and silicon were wet-mixed in a weight ratio of 2:25:73 using isopropyl alcohol (IPA) solvent and spray-dried. Subsequently, the dried product was carbonized at 900°C to obtain a silicon-carbon composite (SCN) (D50: approx. 13㎛).
[0304] (Manufacturing of lithium batteries (full cell), dry cathode)
[0305] Example 1: Dry cathode film comprising graphite, GB 0.5%, and a binder
[0306] (Manufacturing of dry cathodes)
[0307] Graphite as the first cathode active material, polytetrafluoroethylene (PTFE) as the dry binder, and the composite (GB) prepared in Preparation Example 1 were fed into a blade mixer in a weight ratio of 97.5:2.0:0.5, and then first dry mixing was performed at 25°C at a speed of 1200 rpm for 10 minutes to prepare a first dry mixture in which the dry cathode active material and the dry binder were uniformly mixed.
[0308] Subsequently, to allow the fiberization of the binder to proceed, the first mixture was further mixed a second time at 25°C at a speed of 5,000 rpm for 20 minutes to prepare the second mixture. No separate solvent was used during the preparation of the first and second mixtures.
[0309] The prepared second mixture was fed into an extruder and extruded to prepare a dry cathode film in the form of a sheet-shaped self-standing film of cathode active material. The pressure during extrusion was 50 MPa. The dry cathode film contained a composite cathode active material having a structure in which a shell containing a composite and / or a milled product thereof was coated on a graphite core.
[0310] A first laminate was prepared by placing a carbon layer as an interlayer on one side of a copper thin film with a thickness of 12 μm, and placing the interlayer on one side of a second anode current collector.
[0311] The intermediate layer was prepared by coating a composition containing a carbon conductive material (Danka black) and polyvinylidene fluoride (PVDF) onto an aluminum thin film and then drying it. The thickness of the intermediate layer placed on one side of the aluminum thin film was approximately 1 μm.
[0312] A dry cathode film, which is a self-supporting film of the cathode active material layer, was placed on the intermediate layer of the prepared first laminate and rolled to manufacture a cathode.
[0313] (Manufacturing of the anode)
[0314] LiNi 0.91 Co 0.05 Al 0.04 A mixture of O2 (hereinafter referred to as NCA91) composite cathode active material, carbon conductive agent (Denka Black), and polyvinylidene fluoride (PVdF) in a weight ratio of 96:2:2 was mixed with N-methylpyrrolidone (NMP) in a mortar and pestle to prepare a slurry.
[0315] The above slurry was bar-coated to a thickness of 40 μm on an aluminum current collector, dried at room temperature, dried once more under vacuum conditions of 120 ℃, and rolled to manufacture an anode.
[0316] (Manufacturing of coin cells)
[0317] Coin cells were each manufactured using the anode and cathode prepared above, with a polypropylene separator (Celgard 3510) and a solution in which 1.15 M LiPF6 and 1.5 wt% vinylene carbonate (VC) were dissolved in EC (ethylene carbonate) + EMC (ethyl methyl carbonate) + DMC (dimethyl carbonate) (2:4:4 volume ratio) as the electrolyte.
[0318] Example 2: Dry cathode film containing graphite, SCN, GB 0.5%, and binder
[0319] Graphite as the first cathode active material, the silicon composite structure (SCN) used in Preparation Example 4 as the second cathode active material, polytetrafluoroethylene (PTFE) as a dry binder, and the composite (GB) prepared in Preparation Example 1 were fed into a blade mixer in a weight ratio of 81.5:15:3:0.5, and then a first dry mixture was prepared in which the dry cathode active material, the dry conductive material, and the dry binder were uniformly mixed by first dry mixing at a speed of 1200 rpm at 25 ℃ for 10 minutes.
[0320] The dry cathode film contained a first composite cathode active material having a structure in which a shell comprising a composite and / or a milled product thereof is coated on a graphite core, and a second composite cathode active material having a structure in which a shell comprising a composite and / or a milled product thereof is coated on a graphite core on an SCN core.
[0321] Example 3
[0322] A coin cell was manufactured in the same manner as in Example 1, except that the cathode was manufactured according to the following process.
[0323] (Manufacturing of the cathode)
[0324] Graphite as the first cathode active material, the silicon composite structure (SCN) used in Preparation Example 4 as the second cathode active material, polytetrafluoroethylene (PTFE) as a dry binder, and the composite (GB) prepared in Preparation Example 1 were fed into a blade mixer in a weight ratio of 40.5:7.5:1:0.2, and then a first dry mixture was prepared in which the dry cathode active material and the dry binder were uniformly mixed by first dry mixing at a speed of 1200 rpm at 25 ℃ for 10 minutes.
[0325] Subsequently, to allow the fiberization of the binder to proceed, the first mixture was further mixed a second time at 25°C at a speed of 5,000 rpm for 20 minutes to prepare the second mixture. No separate solvent was used during the preparation of the first and second mixtures.
[0326] The prepared second mixture was fed into an extruder and extruded to prepare a first dry cathode film in the form of a sheet-shaped self-standing film of a cathode active material layer. The pressure during extrusion was 50 MPa. The dry cathode film contained a composite cathode active material having a structure in which a shell containing a composite and / or a milled product thereof was coated on a graphite core.
[0327] Separately, a second dry cathode film was prepared by carrying out the same process as above, except that when preparing the second dry mixture for forming the second dry cathode film, the first cathode active material graphite, the second cathode active material silicon composite structure (SCN) used in Preparation Example 4, the dry binder polytetrafluoroethylene (PTFE), and the composite (GB) prepared in Preparation Example 1 were changed to a weight ratio of 40.5:7.5:2:0.3.
[0328] A first laminate was prepared by placing a carbon layer as an interlayer on one side of a copper thin film with a thickness of 12 μm, and placing the interlayer on one side of a second anode current collector.
[0329] The intermediate layer was prepared by coating a composition containing a carbon conductive material (Danka black) and polyvinylidene fluoride (PVDF) onto an aluminum thin film and then drying it. The thickness of the intermediate layer placed on one side of the aluminum thin film was approximately 1 μm.
[0330] A first dry cathode film and a second dry cathode film were sequentially placed on the intermediate layer of the prepared first laminate and rolled to manufacture a dry cathode (copper thin film / intermediate layer (carbon layer) / first dry cathode film / second dry cathode film).
[0331] Example 4
[0332] A coin cell was manufactured in the same manner as Example 2, except that the cathode shown in Fig. 4c was manufactured according to the following process.
[0333] (Manufacturing of dry cathodes)
[0334] Graphite, the silicon composite structure (SCN) used in Preparation Example 4 as the second cathode active material, polytetrafluoroethylene (PTFE) as a dry binder, and the composite (GB) prepared in Preparation Example 1 were fed into a blade mixer in a weight ratio of 40.75:15:2:0.3, and then a first dry mixture was prepared in which the dry cathode active material and the dry binder were uniformly mixed by first dry mixing at a speed of 1200 rpm at 25 ℃ for 10 minutes.
[0335] Subsequently, to allow the fiberization of the binder to proceed, the first mixture was further mixed a second time at 25°C at a speed of 5,000 rpm for 20 minutes to prepare the second mixture. No separate solvent was used during the preparation of the first and second mixtures.
[0336] The prepared second mixture was fed into an extruder and extruded to prepare a first dry cathode film in the form of a sheet-shaped self-standing film of a cathode active material layer. The pressure during extrusion was 50 MPa. The dry cathode film contained a composite cathode active material having a structure in which a shell containing a composite and / or a milled product thereof was coated on a graphite core.
[0337] Separately, a second dry cathode film was prepared by carrying out the same process as above, except that the first cathode active material, graphite, the dry binder, polytetrafluoroethylene (PTFE), and the composite (GB) prepared in Preparation Example 1 were changed to a weight ratio of 40.75:1:0.2 when preparing the first dry mixture.
[0338] A first laminate was prepared by placing a carbon layer as an interlayer on one side of a copper thin film with a thickness of 12 μm, and placing the interlayer on one side of a second anode current collector.
[0339] The intermediate layer was prepared by coating a composition containing a carbon conductive material (Danka black) and polyvinylidene fluoride (PVDF) onto an aluminum thin film and then drying it. The thickness of the intermediate layer placed on one side of the aluminum thin film was approximately 1 μm.
[0340] A first dry cathode film and a second dry cathode film were sequentially placed on the intermediate layer of the prepared first laminate and rolled to manufacture a dry cathode (copper thin film / intermediate layer (carbon layer) / first dry cathode film / second dry cathode film).
[0341] Example 5
[0342] A coin cell was manufactured in the same manner as in Example 3, except that the cathode shown in Fig. 4b was manufactured according to the following manufacturing process.
[0343] (Manufacturing of the cathode)
[0344] Graphite as the first cathode active material, the silicon composite structure (SCN) used in Preparation Example 4 as the second cathode active material, polytetrafluoroethylene (PTFE) as a dry binder, and the composite (GB) prepared in Preparation Example 1 were fed into a blade mixer in a weight ratio of 40.5:7:1:0.2, and then a first dry mixture was prepared in which the dry cathode active material and the dry binder were uniformly mixed by first dry mixing at a speed of 1200 rpm at 25 ℃ for 10 minutes.
[0345] Subsequently, to allow the fiberization of the binder to proceed, the first mixture was further mixed a second time at 25°C at a speed of 5,000 rpm for 20 minutes to prepare the second mixture. No separate solvent was used during the preparation of the first and second mixtures.
[0346] The prepared second mixture was fed into an extruder and extruded to prepare a first dry cathode film in the form of a sheet-shaped self-standing film of a cathode active material layer. The pressure during extrusion was 50 MPa. The dry cathode film contained a composite cathode active material having a structure in which a shell containing a composite and / or a milled product thereof was coated on a graphite core.
[0347] Separately, a second dry cathode film was prepared by carrying out the same process as above, except that when preparing the second dry mixture for forming the second dry cathode film, the first cathode active material graphite, the second cathode active material silicon composite structure (SCN) used in Preparation Example 4, the dry binder polytetrafluoroethylene (PTFE), and the composite (GB) prepared in Preparation Example 1 were changed to a weight ratio of 40.5:8:2:0.3.
[0348] A first laminate was prepared by placing a carbon layer as an interlayer on one side of a copper thin film with a thickness of 12 μm, and placing the interlayer on one side of a second anode current collector.
[0349] The intermediate layer was prepared by coating a composition containing a carbon conductive material (Danka black) and polyvinylidene fluoride (PVDF) onto an aluminum thin film and then drying it. The thickness of the intermediate layer placed on one side of the aluminum thin film was approximately 1 μm.
[0350] A first dry cathode film and a second dry cathode film were sequentially placed on the intermediate layer of the prepared first laminate and rolled to manufacture a dry cathode (copper thin film / intermediate layer (carbon layer) / first dry cathode film / second dry cathode film).
[0351] Comparative Example 1: Preparation of a wet cathode
[0352] (Manufacturing of the cathode)
[0353] Graphite as the first cathode active material, polytetrafluoroethylene (PTFE) as the binder, and the composite (GB) prepared in Preparation Example 1 as the conductive material were fed into a blade mixer in a weight ratio of 96.5:3:0.5, mixed at 25°C at a speed of 1200 rpm for 10 minutes, and then water was added and mixed to obtain a cathode active material slurry.
[0354] After applying the above cathode active material slurry to a copper foil, a film was formed using a doctor blade to achieve a coating thickness of 20㎛, vacuum dried at 130℃ for 3 hours, and then rolled to manufacture a cathode.
[0355] Comparative Example 2: Preparation of a dry cathode
[0356] A dry cathode was prepared in the same manner as in Example 1, except that Denka Black was used instead of the composite prepared in Preparation Example 1 when preparing the first dry mixture.
[0357] Comparative Example 3: Preparation of a dry cathode
[0358] A dry cathode was prepared in the same manner as in Example 2, except that when preparing the first dry mixture, only the silicon composite structure (SCN) used in Preparation Example 4 was used instead of the graphite, which is the first cathode active material, and the silicon composite structure (SCN) used in Preparation Example 4, which is the second cathode active material.
[0359] Evaluation Example 1: Tensile Strength Evaluation
[0360] For each of the dry cathode films prepared in Examples 1-4 and Comparative Examples 1-3, specimens for measuring tensile strength according to ASTM D 638 (216 mm (Length) × 19±0.5 mm (Width) × 3.18±0.38 mm (Depth)) were prepared. Tensile strength was measured by performing a tensile strength test according to the ASTM D 638 method. The measurement results are shown in Table 1 below.
[0361] division Tensile strength [kPa] Before rolling After rolling Example 1 630 1050 Example 2 700 1090 Example 3 1000 1500 Example 4 800 1200 Example 5 1100 1800 Comparative Example 1 50 100 Comparative Example 2 400 960 Comparative Example 3 650 990
[0362] As shown in Table 1, the dry cathode film of Examples 1-4 showed improved mechanical strength compared to the dry cathode of Comparative Examples 1-3.
[0363] It was determined that the dry cathodes of Examples 1 and 2 had each component more uniformly distributed and the binder more uniformly distributed within the dry cathode film and the fiberized binder more effectively bound the composite cathode active material compared to the wet cathode of Comparative Example 1 and the dry cathode of Comparative Example 2.
[0364] Evaluation Example 2: Evaluation of Mixture Resistance
[0365] For each of the dry cathodes prepared in Examples 1-5 and Comparative Examples 1-3, the composite resistance was measured at 25°C using an electrode resistance measurement system (Hioki, RM2610), and the measurement results are shown in Table 3 below.
[0366] In an electrode resistance measurement system (Hioki, RM2610), a probe was placed on the anode so that the cathode active material layer of the cathode faced the probe, a constant current was passed through the surface of the cathode active material layer, and the volume resistivity of the cathode active material layer and the interface resistance between the cathode active material layer and the cathode current collector were measured from the surface potential distribution. The volume resistivity of the cathode active material layer was considered as the composite resistance of the cathode active material layer.
[0367] Evaluation Example 3: Interfacial Resistance Evaluation
[0368] For each of the dry cathodes prepared in Examples 1-5 and Comparative Examples 1-2, the interfacial resistance was measured at 25°C using an electrode resistance measurement system (Hioki, RM2610), and the measurement results are shown in Table 2 below.
[0369] In an electrode resistance measurement system (Hioki, RM2610), a probe was placed on the cathode so that the cathode active material layer of the cathode faced the probe, a constant current was passed through the surface of the cathode active material layer, and the volume resistivity of the cathode active material layer and the interface resistance between the cathode active material layer and the cathode current collector were measured from the surface potential distribution.
[0370] division Combined resistance [Ωcm] Interfacial resistance [Ωcm] 2 ] Example 1 0.035 0.002 Example 2 0.025 0.002 Example 3 0.015 0.001 Example 4 0.02 0.002 Example 5 0.011 0.001 Comparative Example 1 0.068 0.05 Comparative Example 2 0.121 0.004 Comparative Example 3 0.08 0.003
[0371] As shown in Table 2, the dry cathode of Examples 1-5 had a reduced composite resistance compared to the dry cathode of Comparative Example 1-3.
[0372] It was determined that the dry cathode of Examples 1-5 had improved electronic conductivity and / or ion conductivity within the dry anode film by including a composite cathode active material in which a shell containing a composite is uniformly disposed on a core.
[0373] It was determined that the wet cathode of Comparative Example 1 and the dry cathode of Comparative Examples 2-3 had reduced electronic conductivity and / or ionic conductivity because they did not contain the composite cathode active material described above.
[0374] As shown in Table 2, the interface resistance of the dry cathode of Examples 1-5 was reduced compared to the dry cathode of Comparative Example 1-3.
[0375] Evaluation Example 4: Adhesion of electrode plates
[0376] Using an adhesion tester (UTM, Instron), the dry cathode specimens prepared in Examples 1-5 and Comparative Examples 1-3 were cut to 150 mm × 15 mm, and the electrodes were attached to double-sided adhesive tape and the force was measured after 90° detachment. The results are shown in Table 3 below.
[0377] division Adhesion of electrode plates [gf / mm] Example 1 3.5 Example 2 4.0 Example 3 5.9 Example 4 4.8 Example 5 6.8 Comparative Example 1 2.95 Comparative Example 2 1.47 Comparative Example 3 2.8
[0378] As shown in Table 3, the wet cathode of Comparative Example 1 showed improved electrode plate adhesion compared to the dry cathode films of Comparative Examples 2 and 3. However, it was found that the dry cathode films of Examples 1-5 showed improved electrode plate adhesion compared to the wet cathode of Comparative Example 1 and the dry cathodes of Comparative Examples 2-3.
[0379] Evaluation Example 5: Evaluation of Charge / Discharge Characteristics at Room Temperature (25℃)
[0380] The lithium batteries prepared in Examples 1 to 5 and Comparative Examples 1-3 were charged at a constant current rate of 0.1 C at 25°C until the voltage reached 4.5 V (vs. Li), and then cut off at a current rate of 0.02 C while maintaining 4.5 V in constant voltage mode. Subsequently, they were discharged at a constant current rate of 0.1 C until the voltage reached 2.75 V (vs. Li) during discharge (formation cycle).
[0381] The lithium battery, having undergone a formation cycle, was charged at a constant current rate of 0.2 C at 25°C until the voltage reached 4.5 V (vs. Li), and then cut off at a current rate of 0.02 C while maintaining 4.5 V in constant voltage mode. Subsequently, it was discharged at a constant current rate of 0.2 C until the voltage reached 2.75 V (vs. Li) during discharge (1 st Cycle). 50 of these cycles th The process was repeated under the same conditions up to the cycle (50 repetitions).
[0382] In all charge / discharge cycles, a 10-minute pause was taken after each charge / discharge cycle. Part of the results of the room temperature charge / discharge experiments are shown in Table 4 below. The initial efficiency is defined by Equation 1 below, and the capacity retention rate is defined by Equation 2 below.
[0383] <Equation 1>
[0384] Initial efficiency[%] = [Discharge capacity in chemistry cycle / Charge capacity in chemistry cycle] × 100
[0385] <Equation 2>
[0386] Capacity retention rate[%] = [50 th Discharge capacity per cycle / 1 st [Discharge capacity per cycle] × 100
[0387] division Initial efficiency (%) Capacity retention rate[%] Example 1 86.2 93 Example 2 84.5 93 Example 3 85.1 94.5 Example 4 85.5 96.8 Example 5 85.8 98.9 Comparative Example 1 86.4 90 Comparative Example 2 79.2 82 Comparative Example 3 78.2 56
[0388] As shown in Table 4, the lithium batteries of Examples 1 to 5 had improved lifespan characteristics compared to the lithium batteries of Comparative Examples 1 to 2.
[0389] It was determined that these improved lifespan characteristics were due to the suppression of the formation of the solid electrolyte film (SEI) on the surface and / or inside the negative electrode active material by the composite coating, thereby suppressing the internal resistance of the lithium battery.
[0390] Evaluation Example 6: XPS Spectrum Evaluation
[0391] XPS spectra were measured using a Qunatum 2000 (Physical Electronics) over time during the preparation process of the composite prepared in Preparation Example 1. XPS spectra of C 1s orbitals and Al 2p orbitals were measured for samples before heating, after 1 minute, after 5 minutes, after 30 minutes, after 1 hour, and after 4 hours, respectively. At the beginning of heating, only the peak for Al 2p orbitals appeared, and no peak for C 1s orbitals appeared. After 30 minutes, the peak for C 1s orbitals appeared clearly, and the size of the peak for Al 2p orbitals decreased significantly.
[0392] After 30 minutes, peaks for C 1s orbitals attributed to CC bonds and C=C bonds due to graphene growth appeared clearly near 284.5 eV.
[0393] As the oxidation number of aluminum decreased over time, the peak position of the Al 2p orbital shifted toward a lower binding energy (eV).
[0394] Therefore, as the reaction proceeds, graphene grows on the Al2O3 particles, and Al2O3, which is the reduction product of Al2O3 x (0 <x<3)가 생성됨을 확인하였다.
[0395] The average content of carbon and aluminum was measured through XPS analysis results in 10 regions of the composite sample prepared in Preparation Example 1. The deviation of the aluminum content for each region was calculated based on the measurement results. The deviation of the aluminum content was expressed as a percentage of the average value and referred to as uniformity. The percentage of the deviation of the aluminum content relative to the average value, i.e., the uniformity of the aluminum content, was 1%. Therefore, it was confirmed that alumina was uniformly distributed within the composite prepared in Preparation Example 1. Explanation of the symbols
[0396] 1 Lithium battery 2 Negative electrode 3 anodes 4 separators 5 Battery case 6 Cap assembly 7 Battery structure 8 Electrode tab 10 cores 20 shells 21 First metal oxide 22 First carbon-based material 23 Second carbon-based material 100 dry cathode active material
Claims
Claim 1 A dry negative electrode active material and a dry binder are included, wherein the dry negative electrode active material comprises a core; and a shell disposed along the surface of the core, the core comprises a carbon-based material; a mixture of a carbon-based material and a silicon-based active material; a composite of a carbon-based material and a silicon-based active material; or a combination thereof, and the shell comprises a composite comprising one or more first metal oxides and a first carbon-based material, wherein the first metal oxide is disposed within a matrix of the first carbon-based material, and the first metal oxide has the chemical formula M a O b (0 <a≤3, 0<b<4, a가 1, 2, 또는 3 이면, b는 정수가 아님)로 표시되며, 상기 M은 원소주기율표 2족 내지 16족 중에서 선택된 하나 이상의 금속이며,상기 제1 금속산화물이 포함하는 금속이 Al, Nb, Mg, Sc, Ti, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn 및 Se 중에서 선택된 하나 이상의 금속이며,상기 제1 금속산화물이 Al2O z (0 <z<3), NbO x (0 <x<2.5), MgO x (0 <x<1), Sc2O z (0 <z<3), TiO y (0 <y<2), ZrO y (0 <y<2), V2O z (0 <z<3), WO y (0 <y<2), MnO y (0 <y<2), Fe2O z (0 <z<3), Co3O w (0 <w<4), PdO x (0 <x<1), CuO x (0 <x<1), AgO x (0 <x<1), ZnO x (0 <x<1), 및 SeO y (0<y<2) 중에서 선택되는 하나 이상인, 건식 음극 필름이며,상기 실리콘계 활물질은 실리콘 복합 구조체를 포함하며, 상기 실리콘 복합 구조체는 실리콘 입자 및 제1 탄소계 물질을 포함하는 실리콘-탄소 복합체, 실리콘 입자와 제2 탄소계 물질이 혼합된 코어 및 이 코어를 둘러싸는 제3 탄소계 물질을 포함하는 실리콘-탄소 복합체 또는 그 조합을 포함하며,상기 건식 바인더가 섬유화(fibrillized) 바인더를 포함하며, 상기 건식 음극 필름의 압연후 인장강도는 1000 kPa 이상인 건식 음극 필름. Claim 2 In claim 1, the dry cathode film is a dry cathode film having a multilayer structure of two or more layers. Claim 3 A dry cathode film according to claim 1, wherein the dry cathode film comprises a first dry cathode film and a second dry cathode film, and the content of the binder of the first dry cathode film and the content of the composite comprising the first metal oxide and the first carbon-based material are each greater than the content of the binder of the second dry cathode film and the content of the composite comprising the first metal oxide and the first carbon-based material. Claim 4 A dry cathode film according to claim 1, wherein the dry cathode film is a self-standing film, the dry cathode film is free of residual processing solvent, and the tensile strength of the dry cathode film before rolling is 450 kPa or more. Claim 5 A dry cathode film according to claim 1, wherein the content of the composite comprising the first metal oxide and the first carbon-based material of the shell is 5% by weight or less based on the total weight of the dry cathode film. Claim 6 delete Claim 7 In claim 1, the shell further comprises a second metal oxide, and the second metal oxide is of the formula M a O c (0 <a≤3, 0<c≤4, a가 1, 2, 또는 3 이면, c는 정수임)로 표시되며,상기 제2 금속산화물이 상기 제1 금속산화물과 동일한 금속을 포함하며,상기 제2 금속산화물의 a 와 c의 비율인 c / a가 상기 제1 금속산화물의 a 와 b의 비율인 b / a에 비하여 더 큰 값을 가지며,상기 제2 금속산화물이 상기 제1 탄소계 재료 메트릭스 내에 배치되는, 건식 음극 필름. Claim 8 In claim 7, the second metal oxide is Al2O3, NbO, NbO2, Nb2O5, A dry cathode film selected from MgO, Sc2O3, TiO2, ZrO2, V2O3, WO2, MnO2, Fe2O3, Co3O4, PdO, CuO, AgO, ZnO, Sb2O3, and SeO2, wherein the first metal oxide is a reduction product of the second metal oxide. Claim 9 A dry cathode film according to claim 1, wherein the carbon-based material and the first carbon-based material are crystalline carbon, amorphous carbon, or a combination thereof, the crystalline carbon is one or more selected from the group consisting of natural graphite, synthetic graphite, graphene, fullerene, and carbon nanotubes, and the amorphous carbon is one or more selected from the group consisting of pitch carbon, soft carbon, hard carbon, mesophase pitch carbide, calcined coke, and carbon fiber. Claim 10 delete Claim 11 delete Claim 12 In claim 1, the dry binder comprises a fluorine-based binder, and the glass transition temperature (T) of the dry binder g A dry cathode film having a temperature of 15 to 100°C and a dry binder content of 0.1 to 5 wt% relative to the total weight of the dry cathode film. Claim 13 A dry cathode film according to claim 1, wherein the dry cathode film further comprises a dry conductive material, wherein the dry conductive material comprises a carbon-based conductive material, wherein the carbon-based conductive material comprises a fibrous carbon-based material with an aspect ratio of 10 or more, a particulate carbon-based material with an aspect ratio of less than 10, or a combination thereof, and wherein the dry conductive material content is 0.1 to 5 wt% with respect to the total weight of the dry cathode film. Claim 14 A dry cathode comprising: a cathode current collector; and a dry cathode film according to any one of claims 1 to 5, 7 to 9, 12 and 13 disposed on one or both sides of the cathode current collector. Claim 15 A dry cathode according to claim 14, wherein the cathode current collector comprises a substrate; and an interlayer disposed between the substrate and the dry cathode film, wherein the interlayer comprises a carbon-based conductive material. Claim 16 In claim 14, the dry cathode film comprises a first dry cathode film disposed adjacent to a cathode current collector and a second dry cathode film disposed above the first dry cathode film, wherein the content of a composite containing a first metal oxide and a first carbon-based material and the content of a binder of the first dry cathode film are greater than the content of a composite containing a first metal oxide and a first carbon-based material and the content of a binder of the second dry cathode film, respectively. Claim 17 In claim 16, the first dry cathode film comprises a carbon-based material and a silicon-based active material as a core of a dry composite cathode active material, the silicon-based active material comprises a silicon composite structure, the second dry cathode film comprises a carbon-based material as a core of a dry composite cathode active material, and the content of the composite comprising the binder of the first dry cathode film, the first metal oxide, and the first carbon-based material is equal to or greater than the content of the composite comprising the binder of the second dry cathode film, the first metal oxide, and the first carbon-based material. Claim 18 In claim 14, the dry cathode film comprises a first dry cathode film disposed adjacent to a cathode current collector and a second dry cathode film disposed on the first dry cathode film, wherein the first dry cathode film comprises a carbon-based material and a silicon-based active material as a core of a dry composite cathode active material, and the second dry cathode film comprises a carbon-based material and a silicon-based active material as a core of a dry cathode active material, and the silicon-based active material of the first dry cathode film and the second dry cathode film comprises a silicon composite structure, and the content of the composite and binder comprising the first metal oxide and the first carbon-based material of the first dry cathode film is equal to or greater than the content of the composite and binder comprising the first metal oxide and the first carbon-based material of the second dry cathode film, and the content of the carbon-based material and silicon-based active material in the first dry cathode film is relative to the content of the carbon-based material and silicon-based active material in the second dry cathode film Dry cathode that is equal to or larger than the one in comparison. Claim 19 A dry cathode according to claim 14, wherein the cathode current collector comprises a base film and a metal layer disposed on one or both sides of the base film, wherein the base film comprises a polymer, wherein the polymer comprises polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof, and the metal layer comprises indium (In), copper (Cu), magnesium (Mg), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. Claim 20 A lithium battery comprising a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode, wherein the negative electrode is a dry negative electrode and the electrolyte comprises a liquid electrolyte, a solid electrolyte, or a combination thereof; wherein the dry negative electrode comprises a negative current collector; and a dry negative electrode film disposed on one or both sides of the negative current collector; wherein the dry negative electrode film comprises a dry negative electrode active material and a dry binder; wherein the dry negative electrode active material comprises a composite negative electrode active material comprising a core; and a shell disposed along the surface of the core, wherein the core comprises a carbon-based material; a mixture of a carbon-based material and a silicon-based active material; a composite of a carbon-based material and a silicon-based active material; or a combination thereof; wherein the shell comprises a composite comprising one or more first metal oxides and a first carbon-based material, wherein the first metal oxide is disposed within a matrix of the first carbon-based material, and the first metal oxide has the chemical formula M a O b (0 <a≤3, 0<b<4, a가 1, 2, 또는 3 이면, b는 정수가 아님)로 표시되며, 상기 M은 원소주기율표 2족 내지 16족 중에서 선택된 하나 이상의 금속이며,상기 제1 금속산화물이 포함하는 금속이 Al, Nb, Mg, Sc, Ti, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn 및 Se 중에서 선택된 하나 이상의 금속이며,상기 제1 금속산화물이 Al2O z (0 <z<3), NbO x (0 <x<2.5), MgO x (0 <x<1), Sc2O z (0 <z<3), TiO y (0 <y<2), ZrO y (0 <y<2), V2O z (0 <z<3), WO y (0 <y<2), MnO y (0 <y<2), Fe2O z (0 <z<3), Co3O w (0 <w<4), PdO x (0 <x<1), CuO x (0<x<1), AgO x (0<x<1), ZnO x (0<x<1), 및 SeO y (0<y<2) 중에서 선택되는 하나 이상인, 리튬전지이며,상기 실리콘계 활물질이 실리콘 복합 구조체를 포함하며, 상기 실리콘 복합 구조체가 실리콘 입자 및 제1 탄소계 물질을 포함하는 실리콘-탄소 복합체, 실리콘 입자와 제2 탄소계 물질이 혼합된 코어 및 이 코어를 둘러싸는 제3 탄소계 물질을 포함하는 실리콘-탄소 복합체 또는 그 조합을 포함하며,상기 건식 바인더가 섬유화(fibrillized) 바인더를 포함하며, 상기 건식 음극 필름의 압연후 인장강도는 1000 kPa 이상인 리튬전지.
Citation Information
Patent Citations
Process for preparation of anode active material
KR1020120081556A
Composite, electrochemical active material composite using the composite, electrode including the same, lithium battery including the same, electroluminescent device including the same, biosensor including the same, semiconductor device including the same, and thermoelectric device including the same
KR1020150141473A
An anode for a lithium ion secondary battery and a secondary battery comprising the same
KR1020220048461A
Electrode, Lithium battery containing electrode and Preparation method thereof
KR1020220126129A
Negative electrode and rechargeable lithium battery including the same
KR1020230017051A